Seismic response of an offshore jacket-type HVSR station in liquefiable seabed using a modified SANISAND model - Wen-Jie Ren; Ling-Yu Xu; Dong Cai; Ye-Jun Sun; Jun Wang; Chen Wang; Zheng-Hai Sha; Feng-Xue Jin; Wei-Yun Chen (Soil Dynamics and Earthquake Engineering, 2026)

In vitro Reconstitution of Syncytin-2 and MFSD2A Reveals their Functional Tethering in Membrane Fusion Initiation - Zhan Xiang; Lu Xu; Ying Li; Sha Sun (The Journal of Membrane Biology, 2026)

pH regulation of 1,2-bis(trimethoxysilyl)ethane hydrolysis pathways for enhanced wet state stability of TEMPO-oxidized cellulose nanofiber aerogels - Aojia Zhang; Rui Teng; Quan Zhang; Xue Liu; Biyao Sun; Chengcheng Suo; Sha Luo; Chunhui Ma; Shouxin Liu; Wei Li (Carbohydrate Polymers, 2026)

Precursor rigidity engineering enables synergistic regulation of closed pores and graphitic domains for balancing energy and power densities in hard carbon anodes - Qiaofeng Huang; Yiwen Sun; Haoliang Lin; Yuhai Wang; Yifan Sha; Weizhen Fan; Litao Shi; Yu Ying; Xianjian Duan; Chunlei Wu; Guang Shi (Chemical Engineering Journal, 2026)

N-type Ag2Te/Mo2TiC2Tx hybrid film for flexible thermoelectric sensing system enabled rapid IoT-enabled fire early warning - Jiahui Li; Zhuxi Sun; Tongyu Sha; Weijia Zong; Qiudi Lu; Zhangping Jin; Hao Xiong; Yannan Xie (Chemical Engineering Journal, 2026)

SlROP4 negatively regulates drought tolerance in tomato - Chao Cheng; Min Li; Bing Sun; Wenhui Huang; Shanwei Li; Qiangnan Feng; Feng Xiong; Sha Li (Plant Science, 2026)

Sedimentary characteristics and palaeo-ocean environment evolution of the Hejiazhai Formation in the early Tonian Period, Western Henan - Boyang Xu; Deshun Zheng; Qianqian Li; Sha Ren; Fengbo Sun; Jiaqi Fu; Xin Wang; Wentong Yang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Reconstruction of a cross-family chitinase cocktail for efficient chitobiose production guided by the secretome of Streptomyces sp. F-3 - Sha Zhao; Feiyue Wen; Xiaomeng Sun; Yining Dong; Sheng Xing; Lushan Wang; Bo Ding; Xiuyun Wu (Food Chemistry, 2026)

In-situ interfacial C–S–Zn bonding in N/S co-doped hard carbon anchoring ZnS for durable and fast sodium storage - Lingling Liu; Chuanyue Yang; Tong Wang; Jingwen Sun; Xu Yao; Ning Sheng; Xiansen Tao; Lin Shi; Jingquan Sha (Chemical Engineering Journal, 2026)

The SeABI5 transcription factor couples ABA signaling with flavonoid antioxidant production to confer cadmium tolerance in Salicornia europaea - Jinchao Zhou; Pengtao Ji; Guangli Liu; Shuanghong Wang; Lu Liu; Chenyi Liu; Guangyu Sun; Sha Xue; Youwei Du; Huike Li (Journal of Hazardous Materials, 2026)

Engineering exposed crystal planes of ZIF-8 to tune the surface coordination environment for stable zinc metal anodes - Yao Dai; Wenhao Li; Huilin Fan; Runguo Zheng; Zhiyuan Wang; Sha Liu; Hongyu Sun; Yanguo Liu (Chemical Engineering Journal, 2026)

Injectable adhesive hydrogel with self-assembled dual-enzyme nanofibers for spatiotemporal modulation of inflammation and axon regeneration after spinal cord injury - Qi Sha; Yuan Li; Zuomeng Wu; Yankai Wang; Yunxiao Fang; Ao Liu; Shunfeng Liu; Yixiang Dong; Lu Ye; Yue Qin; Shuhui Sun; Junjie Zhao; et al. (Chemical Engineering Journal, 2026)

Enclosure declines plant diversity and homogenization compared to grazing in a Tibetan alpine meadow - Sha Zhu; Yinzhan Liu; Shuang Xiang; Shucun Sun (Agriculture, Ecosystems & Environment, 2026)

Integrative multi-omics identifies CYP1B1 as a candidate molecular link between toxicant exposure and ferroptosis-related epithelial stress in COPD - Lingfeng Liu; Mingjun Jiang; Muzi Lei; Kun Du; Xiangyang Ye; Dafei Wei; Xiaowu Tan; Zhuang Mi; Yao Tang; Ruiting Sun; Sha Liu (Inflammation Research, 2026)

Learning nonlinearity and measuring uncertainty--a multi-task neural network and additive gaussian process based travel choice model - Sha Zhang; Yao Dong; Peter J. Jin; Shichao Sun; Fei Yang (Travel Behaviour and Society, 2026)

Hybrid H2 storage in ZIF-8 and THF-driven Hydrates: A molecular simulation study at the microsecond scale - Fengyi Mi; Hongjuan Sun; Wei Li; Bin Fang; Zhun Zhang; Bowen Sha; Thijs J.H. Vlugt; Othonas A. Moultos; Fulong Ning (Fuel, 2026)

B-site electronic regulation enables decoupling of activity and CO2 tolerance in double perovskite air electrodes for reversible solid oxide cells - Mengyuan Liu; Fangjun Jin; Yaqiong Guo; Yuhang Sha; Ning Sun; Wenjing Zhang; Kun Zheng; Xinxin Wang; Yihan Ling (Chemical Engineering Journal, 2026)

Construction of a scaffold-mediated dual-enzyme display system in Komagataella phaffii with immobilized cells for continuous biocatalysis - Chaowei Zhou; Fanyu Chen; Jing Leng; Caice Liang; Yu Sha; Wenjun Sun; Huanqing Niu; Yong Chen; Hanjie Ying (Bioresource Technology, 2026)

RUBY-BD: a highly efficient visual reporter system for assessing bidirectional promoter activity - Qi Sha; Wen Zhou; XinYan Zhao; YaWen Zhan; Peng Lv; Yujie Gong; YongWang Sun (Planta, 2026)

PM2.5-attributable chronic disease burden in BRICS–plus countries, 1990–2021: temporal trends and health benefits from optimal control - Jiachang Wei; Mengfei Yang; Yiyang Sun; Quanxi Ge; Sha Yang; Guanran Wang; Jing Ding; Sihan Sun; Li Li (Air Quality, Atmosphere & Health, 2026)

Molecular phylogeny and fossil records reveal the origin and evolutionary history of deep-sea Ophiuroidea - Han Yan; Zhongli Sha; Shao’e Sun (Frontiers in Marine Science, 2026)
Introduction The evolutionary history and biogeographic assembly of deep-sea Ophiuroidea remain incompletely understood. This study aimed to clarify the origin, spatial evolution, and long-term assembly of deep-sea ophiuroid diversity through an integrative framework. Methods We integrated multiple lines of evidence, including fossil paleogeography, taphonomic-control analyses, global biogeographic regionalization, directional dispersal asymmetry, time-calibrated molecular phylogenetic analysis, quantitative assessment of species diversification rates, and ancestral-area reconstruction. Results Fossil paleogeographic reconstructions reveal that early ophiuroid occurrences were mainly associated with shallow continental margins at low to middle paleolatitudes, followed by broader spatial expansion during the Paleozoic and a pronounced western Tethyan signal during key Mesozoic intervals. Taphonomic-control analyses show that this western Tethyan concentration remained evident after accounting for preservation opportunity, supporting the importance of this region in the historical distribution of Ophiuroidea. Analyses of extant deep-sea Ophiuroidea show that modern diversity is concentrated mainly in the Indo-Pacific, southwestern Pacific region, and the Gulf of Mexico tropical western Atlantic. Directional dispersal analyses further indicate compositional asymmetry among regions, with a strong western southern Pacific influence at the whole deep-sea scale. Depth-stratified regionalization reveals marked faunal differentiation in the mid-bathyal zone, followed by broader cross-basin connectivity in the lower bathyal and abyssal zones. Molecular dating suggests that deep-sea-associated ophiuroid lineages began to diverge in the late Paleozoic, whereas ancestral-area reconstruction highlights the importance of the Indo-Pacific region in the later biogeographic history of the sampled taxa. Diversification analyses indicate a non-constant evolutionary tempo, with temporal signals broadly consistent with repeated environmental restructuring and post-extinction ecological recovery. Conclusion Overall, these results suggest that deep-sea ophiuroid diversity was assembled through a multi-stage and multi-regional process involving ancient Tethyan historical signals, later Indo-Pacific and Pacific-centered accumulation, depth-dependent connectivity, and recurrent ecological reorganization through geological time.

Enhanced deep nitrogen removal from low C/N wastewater via manganese-catalyzed iron-carbon micro-electrolysis coupled biological system: performance, mechanism, and microbial adaptability - Hengyuan Liu; Kai Wang; Feng Sha; Haibing Che; Rui Sun; Xiuhua Li (World Journal of Microbiology and Biotechnology, 2026)

Double-row jet erosion law of polymetallic nodules considering multi-parameter and flow field variations - Fei Sha; Kairui Yang; Hongying Niu; Weiqiang Sun; Zimeng Qi (Ocean Engineering, 2026)

Bidirectional interfacial polymerization-architected nanoporous graphene-polyamide nanofilms for efficient antibiotic separation - Yumin Sun; Yongbo Yang; Sha Liang; Yihang Zhang; Qinglin Huang; Xutong Han; Changfa Xiao; Wei Li; Kaikai Chen; Xianhui Li; Yang Yang; Hailiang Liu (Chemical Engineering Journal, 2026)

Response of offshore wind turbine monopile-liquefiable seabed-seawater coupled system to vertical and horizontal seismic excitations - Chen Wang; Jia-Jia Xu; Ye-Jun Sun; Jun Wang; Fei Cai; Dong Cai; Zheng-Hai Sha; Feng-Xue Jin; Ling-Yu Xu (Frontiers in Marine Science, 2026)
A comprehensive understanding of the underlying mechanisms governing offshore wind turbine (OWT) response in liquefiable seabeds during seismic events remains incomplete, particularly with respect to vertical ground motion components and tripartite seawater-structure-soil interaction dynamics. A 3D integrated monopile-seabed-seawater model for a monitored 6.45-MW OWT is developed, featuring acoustic elements for seawater hydrodynamics, advanced constitutive models for liquefaction and material damping, and coupled vertical-horizontal seismic input. The dynamic characteristic of the OWT is rigorously validated through ​continuous vibration acceleration monitoring. Key findings reveal that: (1) Increasing monopile embedment depth in non-liquefied soil layers effectively mitigates liquefaction-induced residual lateral displacements; (2) Monopile vertical displacement amplitude depends critically on both seismic input frequency and the phase difference between horizontal/vertical peak ground accelerations; (3) Seawater presence restrains monopile displacements, while neglecting seabed-seawater coupling leads to underestimated excess pore water pressure (EPWP) buildup in shallow seabed layers during seismic events; (4) Vertical seismic motion dominates seawater’s influence on OWT seismic response by coupling with hydrodynamic pressure to amplify the EPWP changes in liquefiable seabeds. The results demonstrate that comprehensive consideration of coupled vertical seismic excitation and fluid-soil-structure interaction is essential for accurate liquefaction assessment of OWT foundations.

Multimodal biosensing of microcystin-LR in environmental and food samples with sensitivity and portability enabled by engineered multimetallic MOF nanozymes - Zhiyong Hu; Ziyue Liu; Yapeng Huo; Yanming Bi; Weicheng Sun; Xinyu Feng; Sha Liu (Food Research International, 2026)

Phase-engineered CdS for ultrafast self-powered photoelectrochemical photodetector in underwater optical communication - Junxin Zhou; Dongxu Jiao; Xinchuan Du; Yunqiu Hua; Sha Zhao; Boya Sun; Xuxuan Yang; Pingan Hu; Yi Wan; Wei Feng (Chemical Engineering Journal, 2026)

Interfacial biomimetic engineering synergizing with mycelium: Constructing high-strength, water-resistant, and flame-retardant formaldehyde-free composites - Junqiang Shan; Yajuan Cao; Yanjun Chen; Yingye Shen; Tianpeng Chen; Yu Sha; Wenjun Sun; Yong Chen; Hanjie Ying (Chemical Engineering Journal, 2026)

Engineering Escherichia coli cell Factories for continuous 5′-cytidine monophosphate production via biofilm-anchored dual-enzyme cascade catalysis - Wenjun Sun; Shiya Zhu; Qiwei Dong; Shuyan Tang; Qingguo Liu; Yu Sha; Tianpeng Chen; Rui Wang; Yong Chen; Hanjie Ying (Bioresource Technology, 2026)

Probiotics as a Therapeutic Strategy for Obesity: New Thoughts on the Stress Response Mechanisms of Probiotics In Vitro and In Vivo - Dingkang Wang; Chao Li; Jingru Ma; Ruijie Xu; Wei Jing; Sha Liu; Xiaomin Sun; Lin Shi; Youfa Wang (Probiotics and Antimicrobial Proteins, 2026)

Quantitative study on the cave environmental factors for the fractionation of stable oxygen isotopes during the deposition of speleothem - Yue Jin; Chun-Jie Wang; Jian Zhang; Wen-Jun Sun; Chao-Jun Chen; Yao Wu; Hua-Yan Li; Yue-Hua Xiang; Yue-Yuan Lin; Xin-Rui Ye; Xin-Yan Li; Zhong-Lin Deng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Genome-wide CRISPR/Cas9 knockout screen identifies host factors essential for bovine parainfluenza virus type 3 replication - Jinyang Hao; Xiaoran Gao; Christine Light; Yuze Sun; Sha Lu; Yu Tian; Xia Gao; Yuan Su; Jie Gao; Xin Huang; Qianyi Zhang; Jinliang Wang; et al. (Science China Life Sciences, 2026)

Double-row jet detachment and initiation characteristics of polymetallic nodules and parameter optimization - Fei Sha; Weiqiang Sun; Hongying Niu; Kairui Yang; Zimeng Qi (Ocean Engineering, 2026)

Double sulfuration promotes the activation of peroxydisulfate by Fe-based N/S co-doped biochar composites to degrade sulfapyridine: Synergistic effect and degradation mechanism - Haozhe Li; Yufeng Sun; Zongtang Liu; Yudong Chen; Zhenghao Fei; Xiankun Wu; Xinlong Sha; Xiaoju Wen; Qirui Guo; Qihui Xu; Yujin Liu; Binbin Qian (Environmental Research, 2026)

Phosphorus-driven regulation of nitrogen configuration in porous carbon for superior lithium storage - Wenwen Wang; Xu Yao; Chuanyue Yang; Yupu Wei; Jingwen Sun; Jingquan Sha; Tai Peng (Chemical Engineering Journal, 2026)

Engineering Escherichia coli for continuous L-valine production via two-stage biofilm and metabolic regulation - Wenjun Sun; Yu Sha; Shuqi Shi; Wenlu Qi; Qingguo Liu; Tianpeng Chen; Yong Chen; Hanjie Ying (Chemical Engineering Journal, 2026)

Near-unity quantum yield blue hybrid cuprous halide with high water resistance for multiple applications - Chenning Sun; Kangkang Wang; Fu Wang; Xiaoxin Zhao; Sha Bai; Binbin Su; Huidong Xie (Chemical Engineering Journal, 2026)

Engineered cytosolic and chloroplastic UDP-glucose epimerases distinctly modulate xylan interplay for size-tunable cellulose nanocrystals production in Oryza sativa - Yumeng Sun; Muzi Li; Meiyun Yang; Wennian Xia; Sha Wang; Zhongyi Wang; Yanting Wang; Liangcai Peng; Huizhen Hu; Ran Zhang (Carbohydrate Polymers, 2026)

Engineering living bio-hybrid materials for sustainable l-threonine production - Shuqi Shi; Jinming Zhang; Shiya Zhu; Yu Sha; Qingguo Liu; Tianpeng Chen; Wenjun Sun; Wei Zhuang; Yong Chen; Hanjie Ying (Bioresource Technology, 2026)

Dual-phase engineering of FeS2/Fe7S8 heterostructures on GO derived from MIL-101 for superior lithium storage - Ziwei Yin; Lingling Liu; Chuanyue Yang; Xu Yao; Ning Sheng; Minghui Zuo; Jingwen Sun; Jingquan Sha (Chemical Engineering Journal, 2026)

Transplantation of Skin-Derived Precursor Schwann Cells Ameliorates Secondary Brain Injury after ICH in Mice by Activating the PI3K/AKT/FOXO3a Signaling Pathway - Yuqian Tang; Yan Song; Qiuwen Sun; Muyuan Tong; Yejing Zhang; Yan Chen; Junyi Sha; Chengbin Xue; Jiabing Shen; Aihong Li (Translational Stroke Research, 2026)

Revolutionary tuned mass damper by carbon fiber powder based shear thickening fluid to realize adaptive stiffness and damping - Li Sun; Tianqi Liang; Meng Hou; Xin Sha; Chunwei Zhang (Soil Dynamics and Earthquake Engineering, 2026)

Linking ENSO diversity to runoff predictability in China using nonhomogeneous hidden Markov model - Jian Sun; Lei Yan; Jinxia Sha; Dan Xu; Fan Lu; Qinghua Luan; Yuan Liu; Boyuan Lu; Cong Jiang; Lihua Xiong (Journal of Hydrology, 2026)

Amplifying 2′3′-cGAMP with “open source throttling” strategy: Intelligent nanoreactors enhance immunotherapy in HNSCC via cascade activation of the cGAS-STING pathway - Tong Sha; Ze Wang; Jinwei Li; Yahong Wu; Xiaoyi Yu; Jinbiao Qiang; Annan Liu; Hao Liang; Zunxuan Xie; Yijun Zhou; Hongchen Sun; Andrew K. Whittaker; et al. (Chemical Engineering Journal, 2026)

Dynamic hydrolytic ion-pairing enables stable interfaces and high anode utilization in lean-electrolyte Mg-air batteries - Yuxi Zhang; Sensen Yu; Ming Li; Sha Luo; Yu Feng; An Duan; Bao Zhang; Wei Sun (Chemical Engineering Journal, 2026)

Cellulose based hierarchical structural colored wood composite material for daytime radiative cooling - Biyao Sun; Shaoyi Cao; Shuliang Dou; Yudong Li; Wenye Sun; Chunhui Ma; Sha Luo; Mingcong Xu; Shouxin Liu; Wei Li (Carbohydrate Polymers, 2026)

Biogenic α-Mn2O3 excels in areas where commercial α-Mn2O3 performs poorly: Native and advanced oxidation degradation of atrazine - Huatao Sun; Huiyan Chen; Wuying Chen; Mingzhen Hu; Sha Chen; Yingjie Ma; Runjun Ou; Ding Li (Journal of Environmental Chemical Engineering, 2025)

Tannic acid-triggered functional coatings for the regulation of surface charge, cell adhesion and semi-continuous fermentation - Yu Sha; Yong Gao; Jinming Zhang; Tianpeng Chen; Qingguo Liu; Chenjie Zhu; Pengpeng Yang; Hanjie Ying; Yong Chen; Wenjun Sun; Wei Zhuang (Journal of Environmental Chemical Engineering, 2025)

Ferritin-alginate oligosaccharide shell core complex for co-encapsulation and synergistic stabilization of astaxanthin and zinc ions - Rui Yang; Jincan Wu; Zexu Li; Yue Li; Chunkai Gu; Xinmei Sha; Li Liang; Shihao Sun; Lei Shi; Yuyu Zhang (Food Hydrocolloids, 2025)

Prevalence and spectrum of STRC variants in 1015 sensorineural hearing loss patients: insights from the Chinese population - Luo Guo; Sha Yu; Wenrui Zhao; Liheng Chen; Guiqing Cheng; Weitao Li; Wei Li; Haiting Ji; Shan Sun; Huiqian Yu; Haiying Liu; Chunyi Gui; et al. (Molecular Genetics and Genomics, 2025)

IFNGR1, IRF8 genetic polymorphisms modulate the susceptibility of non-tuberculous mycobacteria pulmonary disease and influence the patients’ treatment outcomes and immune status - Li-ping Cheng; Zhi-bin Liu; Lei Wang; Jie Cao; Qing-rong Qu; Hai Lou; Xiao-na Shen; Juan Yang; Yuanyuan Yu; Rui Juan Zheng; Wei Sha; Qin Sun (Inflammation Research, 2025)

Transcriptome analysis reveals no obvious unintended effects in the spleen of CRISPR/Cas9-mediated CD163 and pAPN double-knockout pigs - Zhi-Guo Liu; Nan Wang; Wan-Jie Wang; Lei Huang; Shun-Shun Chi; Yu-Xin Nie; Mao-Sha Yuan; Ya-Ru Sun; Yu-Lian Mu; Kui Li (Functional & Integrative Genomics, 2025)

Chronic dietary exposure to BDE-47 can induce inflammatory responses in the brain of common carp (Cyprinus carpio) and further trigger neurotoxicity through the 5-HT pathway - Huimin Sun; Youlian Liu; Yujie Huang; Mengbin Yuan; Zujun Ye; Rong Yang; Fuqiang Sha; Ni Tang; Bo Zhou; Defang Chen; Zhiqiong Li; Xin Zhang (Science of The Total Environment, 2025)

Insights into the combined effect of ofloxacin and humic substances on sewage sludge anaerobic digestion - Sha Long; Zhixiang Hao; Luyang Sun; Dejiang Ren; Keyi Wang; Huiming Li; Dongbo Wang (Environmental Research, 2025)

Pyrite-activated peracetic acid for enhanced sludge dewaterability: Molecular insights into reactive species generation and interfacial interaction mechanisms - Zhihua Mo; Jiapeng Zhong; Lanrong Zhao; Yuqiong Li; Rongyue Wang; Pengzhan Sha; Jialin Liang; Shuiyu Sun; Wei Guo; Jinxi Feng; Kengbo Ding; Chuanhao Li (Chemical Engineering Journal, 2025)

Unveiling dynamics of microbial communities, species interactions, and ecological assembly during low-temperature-induced sludge bulking in full-scale wastewater treatment systems - Han-Jun Sun; Xian Zhao; Jie Ding; Yu-Qian Wang; Wen-Shuo Wang; Zhi-Hua Feng; Sha Zhao; Liang Wang; Nan-Qi Ren; Shan-Shan Yang (Bioresource Technology, 2025)

Disrupted Lipid Metabolism Aggravates Ischemic Brain Injury: Targeting FDFT1 for Stroke Therapy - Jing Yuan; Yu-Sha Liao; Tie-Chun Zhang; Shuang Liu; Min-Min Ruan; Ting-Ting Yang; Shi-Qi Sun; Long-Yao Xu; Xiao-Long Xie; Ling Zhao (Molecular Neurobiology, 2025)

Has the application of agricultural green technologies achieved carbon reduction? Evidence from China - Shilong Meng; Yanjun Jiang; Hongwu Sun; Yanfei Sha; Ruiyao Ying (Clean Technologies and Environmental Policy, 2025)

Middle Campanian to Maastrichtian foraminifera and biomarkers: Seawater incursion events in the Songliao Basin, Northeast China - Ke-Ying Yue; Sha Li; Tian Jiang; Dang-Peng Xi; Bo-Wen Song; Yu Liang; Li-Xin Sun; Tian-Fu Zhang; Hai-Chun Zhang; Xiao-Qiao Wan; Bo Wang (Palaeoworld, 2025)

Changes in physical properties and characteristic peptides in porcine gelatin-containing gummy candies at different storage stages during shelf-life - Le-Ying Yang; Zong-Cai Tu; Hui Wang; Xue-Ke Sun; Yu-Ting Hu; Yu Chen; Zi-Zi Hu; Xiao-Mei Sha (Food Hydrocolloids, 2025)

Precise Magnetic Stimulation of the Paraventricular Nucleus Improves Sociability in a Mouse Model of ASD - Sha Liu; Quyang Yang; Pengfei Zhu; Xuan Liu; Qingbo Lu; Jie Yang; Jingyao Gao; Hongbin Han; Zhijun Zhang; Ning Gu; Tao Tan; Jianfei Sun (Neuroscience Bulletin, 2025)
Magnetic stimulation has made significant strides in the treatment of psychiatric disorders. Nonetheless, current magnetic stimulation techniques lack the precision to accurately modulate specific nuclei and cannot realize deep brain magnetic stimulation. To address this, we utilized superparamagnetic iron oxide nanoparticles as mediators to achieve precise targeting and penetration. We investigated the effects of magnetic fields with varying frequencies on neuronal activity and compared the activation effects on neurons using a 10-Hz precise magneto-stimulation system (pMSS) with repetitive transcranial magnetic stimulation in mice. Oxytocin levels, dendritic morphology and density, and mouse behavior were measured before and after pMSS intervention. Our findings suggest that pMSS can activate oxytocinergic neurons, leading to upregulation of oxytocin secretion and neurite outgrowth. As a result, sociability was rapidly improved after a one-week pMSS treatment regimen. These results demonstrate a promising magneto-stimulation method for regulating neuronal activity in deep brain nuclei and provide a promising therapeutic approach for autism spectrum disorder.

Breaking wild soybean seed physical dormancy: optimal methods and seed coat structural changes - Yujie Gong; Dongxue Zhang; Jiaqi Lv; Peng Lv; Xinyan Zhao; Qi Sha; Wen Zhou; Yongwang Sun (Genetic Resources and Crop Evolution, 2025)

Damage to survival, development, and growth of Japanese flounder (Paralichthys olivaceus) at early developmental stages by Ulva prolifera decay - Weijun Zhang; Kunpeng Shi; Jiacheng Sun; Haibo Zhang; Suxu Tan; Xiaoyong Shi; Jinqi Xia; Muyuan Wang; Ningning Wang; Jie Ma; Zhenxia Sha (Harmful Algae, 2025)

Protective effects of rosmarinic acid against oxidative damage and atherosclerosis via the PI3K/AKT pathway - Tiantian Tang; Mingze Sun; Baiyuan Sha; Rui Liu; Zhiyang Ren; Liwei Li; Ye Zhang; Hao Wang; Kai Yu (Food and Chemical Toxicology, 2025)

Surface wrinkle modulated pyridinic nitrogen-rich zincophilic sites for stable, fast and uniform zinc deposition - Yao Dai; Shihong Dong; Jianxing Wang; Runguo Zheng; Zhiyuan Wang; Sha Liu; Zhishuang Song; Hongyu Sun; Yanguo Liu (Chemical Engineering Journal, 2025)

Field-validated Mg-biochar balls: In-situ nutrient recovery from Paddy runoff and compost enhancement for economic benefits - Xinyue Lu; Lisha Wang; Xiaolong Sun; Wenjing Guo; Aiguo Sha; Yuanyuan Feng; Yanfang Feng; Lihong Xue (Chemical Engineering Journal, 2025)

Landfill depths alter microbial community structure and ecological assembly by affecting δ13C and organic matter - Yu-Xin Wang; Qing-Yu Liu; Jun-Yan Du; Hao-Qun Sha; Jing Su; Yue Sun; Jing-Ying Mao; Xiao-Song He (Waste Management, 2025)

A novel bioreactor developed for the intensification of high-viscosity aerobic fermentation processes - Qian Chen; Kai Hu; Quanfei Li; Kai Yang; Chao Zhang; Weiwei Huang; Yibin Qiu; Yian Gu; Liang Sun; Peng Lei; Jian Xue; Sha Li; et al. (Chemical Engineering Journal, 2025)

Continuous manufacturing of solvent-driven poly(vinyl alcohol)-based flexible electrodes with vias conductive gels for sensitive skin-integrated electronics - Dongyong Sha; Ding Ding; Shuaimin Tang; Jianxing Zhang; Xuan Tang; Changsheng Liu; Xiaofeng Ling; Lili Sun; Yuan Yuan (Chemical Engineering Journal, 2025)

NC coating MOF-derived CoFe2O4/C spinel for high performance lithium-ion batteries anode - Wenwen Wang; Xu Yao; Zhaochun Ma; Jinlong Zhuo; Zhihua Lu; Jingwen Sun; Jiwen Cui; Jingquan Sha (Chemical Engineering Journal, 2025)

A new species of genus Thalassometra AH Clark, 1907 (Crinoidea: Tropiometroidea: Thalassometridae) from a seamount on the Caroline Ridge in the northwest Pacific - Shao’e Sun; Zijie Mei; Zhongli Sha (Journal of Oceanology and Limnology, 2025)

Improvement of gastrointestinal digestive resistance of probiotics by interfacially cross-linked water-in-water emulsions - Yudong Sun; Sha Ao; Congying Zhou; Huaqiang Cao; Junxia He; Yuan Wang; Shilin Liu (Food Hydrocolloids, 2025)

Dissipation of Ulva prolifera green tides across various spatial and temporal scales and the short-term effects on marine environments - Jiacheng Sun; Ke Liu; Haibo Zhang; Jie Fu; Xiaoyong Shi; Ziwei Yao; Gang Zhao; Zhenxia Sha; Hao Cui; Jinpeng Wu (Marine Environmental Research, 2025)

Bismuth-selenium nanocomposite clusters inhibit tobacco bacterial wilt by disrupting bacterial morphology and promoting vegetative oxidative phosphorylation - Yanyu Hu; EnDong Yang; Yanping Qiu; Bangjia Yang; Shenghui Gao; Sha Li; Yuanyuan Cao; Dongdong Sun (Journal of Cleaner Production, 2025)

Multiple stimuli-responsive circularly polarized luminescent bio-composite films by coassembling cellulose nanocrystals and curcumin - Shaoyi Cao; Jingpeng Wang; Wenye Sun; Bang An; Mingcong Xu; Sha Luo; Chunhui Ma; Haipeng Yu; Zhijun Chen; Jian Li; Wei Li; Shouxin Liu (Carbohydrate Polymers, 2025)

Response of vegetation evapotranspiration to landscape pattern changes in an arid region: A case study of the Loess Plateau, China - Jin Guo; Liangxin Fan; Pengfei Feng; Xialing Sun; Sha Xue (CATENA, 2025)

SYMRK significantly affected AMF symbiosis and plant growth in maize - Jing Zhou; Sha Lin; Xinhao Luo; Lixue Sun; Jin Chen; Beijiu Cheng; Xiaoyu Li (Plant Science, 2025)

Biogeographic dynamics of graptolites during the Late Ordovician Mass Extinction in South China - Lin-Na Zhang; Sha-Sha Sun; Zong-Yuan Sun; Ming-Feng Lu; Qing Chen (Palaeoworld, 2025)

The community succession mechanisms and interactive dynamics of microorganisms under high salinity and alkalinity conditions during composting - Qing-Yu Liu; Yu-Xin Wang; Hao-Qun Sha; Hao-Min Zhou; Yue Sun; Jing Su; Ying Mei; Xin Dai; Xiao-Song He (Journal of Environmental Management, 2025)

A lightweight “brick–mortar” honeycomb composite via hollow carbon spheres as skeleton for electromagnetic shielding and Joule heating - Jianshu Wang; Ying Sha; Zhihao Sun; Zihao Guo; Jingyu Bi; Zeqi Liu; Hao Wang; Chaoxuan Wang; Lei Qian (Chemical Engineering Journal, 2025)

Stable liposomal cerasome for ultrasound/H2O2-activated CO release to augment tumor chemotherapy and immunotherapy - Suhui Sun; Ruiqi Wu; Shiti Sha Ma; Zhong Cao; Liang Luo; Sujuan Sun; Ligang Cui; Xiaolong Liang (Chemical Engineering Journal, 2025)

Multi-organ toxicity caused by PM2.5 in mice with cardiovascular diseases: The role of PAHs played from the most polluted episodes in China - Jinjin Yu; Jian Sun; Yajing Ma; Xinyi Niu; Ruisi Zhu; Huixin Song; Lingyi Liu; Yuzhi Luo; Songyuan Xia; Jingyu Wang; Lingli Li; Sha Wen; et al. (Journal of Environmental Management, 2025)

Synergistic governance efficiency of industrial pollution and CO2 emissions under the digital economy - Sha Sun; Mingming Zhang; Liyun Liu; Dequn Zhou (Journal of Environmental Management, 2025)

Biomonitoring and food surveillance on heavy metals reveal need for food safety in a coastal region - Xin Zhang; Xiaoqian Yang; Xiaoyue Hu; Zhonghua Meng; Zhigang Yu; Zhan Sun; Ying Zhang; Zhifeng Yang; Sha Li; Jia-Sheng Wang; Qiang Jia; Lanzheng Liu; et al. (Food Research International, 2025)

Water-in-water Pickering emulsions as a fascinating culture and embedding medium for Saccharomyces cerevisiae - Sha Ao; Yudong Sun; Xiaoqi Ding; Congying Zhou; Yuan Wang; Junxia He; Huaqiang Cao; Yan Li; Bin Li; Shilin Liu (Food Bioscience, 2025)

Kiwifruit polyphenols regulate mitophagy to promote intestinal barrier function: Based on proteomics, in vitro and in vivo study - Ruiyu Xu; Yan Zhou; Hongyan Niu; Sha Xue; Lijun Fu; Qun Huang; Yong Sun (Food Bioscience, 2025)

Creating rich closed nanopores in anthracite-derived soft carbon enables greatly-enhanced sodium-ion storage in the low-working-voltage region - Jiawei Gu; Yiwei You; Miao Liu; Ling Huang; Zhefei Sun; Junjie Liu; Liyuan Sha; Minghui Chen; Sha Li; Shunqing Wu; Qiaobao Zhang; Li Zhang (Chemical Engineering Journal, 2025)

Enhancing the application of probiotics in probiotic food products from the perspective of improving stress resistance by regulating cell physiological function: A review - Dingkang Wang; Ruijie Xu; Sha Liu; Xiaomin Sun; Tianxiao Zhang; Lin Shi; Youfa Wang (Food Research International, 2025)

Optimizing energy efficiency in buildings’ cold water systems: A differential pressure control-based global approach - Jinhui Tang; Le Sha; Hejiang Sun; Wenshuai Zhang (Energy and Buildings, 2025)

Abnormal upregulation of NUBP2 contributes to cancer progression in colorectal cancer - Danfeng Lan; Junyu Wang; Guishun Sun; Lixia Jiang; Qiyun Chen; Sha Li; Haiyan Qu; Yibo Wang; Bian Wu (Molecular and Cellular Biochemistry, 2025)
Colorectal cancer (CRC), a digestive tract malignancy with high mortality and morbidity, lacks effective biomarkers for clinical prognosis due to its complex molecular pathogenesis. Nucleotide binding protein 2 (NUBP2) plays a vital role in the assembly of cytosolic Fe/S protein and has been implicated in cancer progression. In this study, we found that NUBP2 was highly expressed in CRC by TCGA database analysis. Subsequently, we verified the expression of NUBP2 in CRC tumor tissues and para-carcinoma tissues using IHC staining, and further investigated its association with clinicopathological parameters. In vitro cell experiments were conducted to assess the role of NUBP2 in CRC by evaluating cell proliferation, migration, and apoptosis upon NUBP2 dysregulation. Furthermore, we established a subcutaneous CRC model to evaluate the impact of NUBP2 on tumor growth in vivo. Additionally, we performed mechanistic exploration using a Human Phospho-Kinase Array-Membrane. Our results showed higher expression of NUBP2 in CRC tissues, which positively correlated with the pathological stage, indicating its involvement in tumor malignancy. Functional studies demonstrated that NUBP2 knockdown reduced cell proliferation, increased apoptosis, and impaired migration ability. Moreover, NUBP2 knockdown inhibited tumor growth in mice. We also observed significant changes in the phosphorylation level of GSK3β upon NUBP2 knockdown or overexpression. Additionally, treatment with CHIR-99021 HCl, an inhibitor of GSK3β, reversed the malignant phenotype induced by NUBP2 overexpression. Overall, this study elucidated the functional role of NUBP2 in CRC progression both in vitro and in vivo, providing insights into the molecular mechanisms underlying CRC and potential implications for targeted therapeutic strategies.

Apoc1 Knockdown Alleviates High Glucose-induced Oxidative Stress and Apoptosis of Renal Tubular Cells by Binding to Clusterin - Liyin Chai; Zhengyang Liu; Jun Zeng; Li Gong; Sha Xiang; Jing Yu; Haili Sun; Chaolin Wen; Fang Wang; Ning Li; Bingbing Shen; Mei Mei (Cell Biochemistry and Biophysics, 2024)

Emissions of gaseous nitrous acid (HONO) from diesel trucks: Insights from real-driving emission experiments - Songdi Liao; Zhipeng Tu; Fei Yu; Manni Zhu; Kaiming Sun; Qinge Sha; Xinping Yang; Junyu Zheng (Science of The Total Environment, 2024)

How does PM2.5 affect forest phenology? Integrating PM2.5 into phenology models for warm-temperate forests in China - Sha Zhao; Yaowen Xie; Guilin Xi; Yanzhe Sun; Haoyan Zhang (Environmental Research, 2024)

One-stone-for-two-birds strategy to construct robust 2D conjugated metal-organic framework-based quasi-solid-state lithium-organic batteries - Jingwen Cao; Xupeng Zhang; Ying Wang; Shuainan Sha; Qiong Wu; Xingwei Sun; Heng-Guo Wang (Chemical Engineering Journal, 2024)

Butterfly wing-inspired superhydrophobic photonic cellulose nanocrystal films for vapor sensors and asymmetric actuators - Bang An; Mingcong Xu; Wenye Sun; Chunhui Ma; Sha Luo; Jian Li; Shouxin Liu; Wei Li (Carbohydrate Polymers, 2024)

Enhancing environmental and economic benefits of constructed wetlands through plant recovery: A life cycle perspective - Xue Zhou; Jixian Yang; Aiqi Sha; Zhixuan Zhuang; Shunwen Bai; Huihang Sun; Xinyue Zhao (Science of The Total Environment, 2024)

Occurrence, spatial distribution, and ecological risk of benzotriazole UV stabilizers (BUVs) in sediments from Bohai sea of China - Xing Liu; Xiaodan Pei; JiaoJiao Li; Yawen Wei; Hao Sun; Zilan Wu; Sha Wang; Jianmin Chen; Zhongsheng Lin; Ziwei Yao (Environmental Research, 2024)

A colorimetric paper based on curcumin-loaded CD-MOFs and CNFs for visual monitoring of strawberry freshness - Qianyu Sun; Jun Chen; Huan Yang; Tianzhong Yuan; Rendang Yang; Daliang Guo; Huifang Zhao; Jing Li; Shangru Zhai; Lizheng Sha (Chemical Engineering Journal, 2024)

Short-term usage of proton pump inhibitors during admission was associated with increased risk of rehospitalization in critically ill patients with myocardial infarction: a cohort study - Jia-De Zhu; Li-Juan Yang; Jian-Nan Zhao; Ping Wang; Yi-Hua Li; Xue-Sha Zhang; Jian-Mei Pan; Meng-Han Jiang; Hai-Ying Yang; Sun-Jun Yin; Gong-Hao He (European Journal of Clinical Pharmacology, 2024)

Carbon nanomaterials-based smart dual-mode sensors for colorimetric and fluorescence detection of foodborne hazards - Feifei Sun; Peiran Li; Guojian Wu; Fengjiao He; Sha Liu; Yizhong Shen; Yongning Wu; Lin Li (Trends in Food Science & Technology, 2024)

The superior adsorption capacity of biogenic α-Mn2O3 in comparison to chemogenic α-Mn2O3 for five divalent heavy metal cations and the adsorption mechanism of biogenic α-Mn2O3: Experimental and DFT investigations - Mingzhen Hu; Huatao Sun; Jun Luo; Sha Chen; Ding Li (Journal of Environmental Chemical Engineering, 2024)

Soil aggregate-associated organic nitrogen pools, enzyme activities, and microbial community fertilized with food waste-derived organic fertilizer - Jun Wang; Zhimin Sha; Qin Qin; Lijuan Sun; Yafei Sun; Shiyan Yang; Yong Xue; Linkui Cao (Applied Soil Ecology, 2024)

Electrical resistivity structure of the Southeastern part of Bayan Har Block: Insights into the seismogenic environment of 2022 Maerkang earthquake swarm - Yan Zhan; Xiangyu Sun; Xuehua Liu; Lingqiang Zhao; Dahu Li; Sha Li; Zeyi Dong; Xiaoyu Lou; Chongtao Hao; Yuxin Bao (Tectonophysics, 2024)

The survival, gene expression, and DNA methylation of Paralichthys olivaceus impacted by the decay of green tide and bacterial infection in both laboratory and field simulation experiments - Jie Ma; Kunpeng Shi; Weijun Zhang; Sen Han; Zhendong Wu; Muyuan Wang; Haibo Zhang; Jiacheng Sun; Ningning Wang; Mengyang Chang; Xiaoyong Shi; Suxu Tan; et al. (Science of The Total Environment, 2024)

Molecular evolution of the mitochondrial genome underlies semi-aquatic adaptation in lutrinae - Qinguo Wei; Xibao Wang; Yuehuan Dong; Xuesong Mei; Yongquan Shang; Guolei Sun; Xiaoyang Wu; Xiaodong Gao; Chao Zhao; Weilai Sha; Honghai Zhang (Organisms Diversity & Evolution, 2024)

NSP4 promotes replication of porcine reproductive and respiratory syndrome virus-2 - Hang Zhang; Gan Li; Yajie Zheng; Qin Luo; Huiyang Sha; Wenchao Sun; Mengmeng Zhao (Veterinary Microbiology, 2024)

Enhancement of efficient molecular biology tools for Tremella fuciformis spore - Caiyuan Yu; Yuanwei Sun; Chunkai Yang; Yan Fang; Qi Meng; Yibin Qiu; Peng Lei; Hong Xu; Qi Zhang; Sha Li (Food Bioscience, 2024)

Adenylate kinase phosphate energy shuttle underlies energetic communication in flagellar axonemes - Huan Wu; Yanman Zhang; Yuqian Li; Shuya Sun; Jintao Zhang; Qingsong Xie; Yue Dong; Shushu Zhou; Xuan Sha; Kuokuo Li; Jinyi Chen; Xin Zhang; et al. (Science China Life Sciences, 2024)

High dimensional proteomic mapping of bone marrow immune characteristics in immune thrombocytopenia - Feng-Qi Liu; Qing-Yuan Qu; Ying Lei; Qi Chen; Yu-Xiu Chen; Meng-Lin Li; Xue-Yan Sun; Ye-Jun Wu; Qiu-Sha Huang; Hai-Xia Fu; Yuan Kong; Yue-Ying Li; et al. (Science China Life Sciences, 2024)

SNX14 inhibits autophagy via the PI3K/AKT/mTOR signaling cascade in breast cancer cells - Sha Lv; Hongyan Jiang; Lingyan Yu; Yafei Zhang; Liangliang Sun; Junjun Xu (Journal of Molecular Histology, 2024)

SAD2 functions in plant pathogen Pseudomonas syringae pv tomato DC3000 defense by regulating the nuclear accumulation of MYB30 in Arabidopsis thaliana - Tiantian Shi; Yuan Zheng; Rui Wang; Sha Li; Andi Xu; Luoying Chen; Yuanhang Liu; Rong Luo; Chenchen Huang; Yinglu Sun; Jinfeng Zhao; Xiaoying Guo; et al. (Plant Science, 2024)

Cross-linking Cu-TCPP@CNT-OH-S as high sulfur loading cathode for Li-S batteries - Mingqi Xu; Xiangyi Liu; Zhe Zhao; Longjiang Sun; Lingling Liu; Jinhang Guo; Jingquan Sha (Chemical Engineering Journal, 2024)

An emerging link between lncRNAs and cancer sex dimorphism - Ikrame Naciri; Maria D. Andrade-Ludena; Ying Yang; Mei Kong; Sha Sun (Human Genetics, 2024)
The prevalence and progression of cancer differ in males and females, and thus, sexual dimorphism in tumor development directly impacts clinical research and medicine. Long non-coding RNAs (lncRNAs) are increasingly recognized as important players in gene expression and various cellular processes, including cancer development and progression. In recent years, lncRNAs have been implicated in the differences observed in cancer incidence, progression, and treatment responses between men and women. Here, we present a brief overview of the current knowledge regarding the role of lncRNAs in cancer sex dimorphism, focusing on how they affect epigenetic processes in male and female mammalian cells. We discuss the potential mechanisms by which lncRNAs may contribute to sex differences in cancer, including transcriptional control of sex chromosomes, hormonal signaling pathways, and immune responses. We also propose strategies for studying lncRNA functions in cancer sex dimorphism. Furthermore, we emphasize the importance of considering sex as a biological variable in cancer research and the need to investigate the role lncRNAs play in mediating these sex differences. In summary, we highlight the emerging link between lncRNAs and cancer sex dimorphism and their potential as therapeutic targets.

Recycling of fly ash to synthesize zeolites for efficient removal of dioxins - Lianzheng Gui; Zhiming Zhang; Ke Sun; Xiong Shi; Sha Liang; Huabo Duan; Zhe Yang; Shushan Yuan; Limin Guo; Jiayu Xu; Jiakuan Yang (Journal of Environmental Chemical Engineering, 2024)

LTA and PGN from Bacillus siamensis can alleviate soybean meal-induced enteritis and microbiota dysbiosis in Lateolabrax maculatus - Zi-Yan Liu; Hong-Ling Yang; Guo-He Cai; Sha Li; Ji-Dan Ye; Chun-Xiao Zhang; Yun-Zhang Sun (Fish & Shellfish Immunology, 2024)

Enhancing hydrological extremes prediction accuracy: Integrating diverse loss functions in Transformer models - Xue Li; Qi-Liang Sun; Yanfei Zhang; Jian Sha; Man Zhang (Environmental Modelling & Software, 2024)

LIPUS regulates the progression of knee osteoarthritis in mice through primary cilia-mediated TRPV4 channels - Sha Wu; Haiqi Zhou; Huixian Ling; Yuyan Sun; Ziyu Luo; ThaiNamanh Ngo; Yuanyuan Fu; Wen Wang; Ying Kong (Apoptosis, 2024)
Osteoarthritis (OA) is a common disease in middle-aged and elderly people. An imbalance in calcium ion homeostasis will contribute to chondrocyte apoptosis and ultimately lead to the progression of OA. Transient receptor potential channel 4 (TRPV4) is involved in the regulation of intracellular calcium homeostasis. TRPV4 is expressed in primary cilia, which can sense mechanical stimuli from outside the cell, and its abnormal expression is closely related to the development of OA. Low-intensity pulsed ultrasound (LIPUS) can alleviate chondrocyte apoptosis while the exact mechanism is unclear. In this project, with the aim of revealing the mechanism of action of LIPUS, we proposed to use OA chondrocytes and animal models, LIPUS intervention, inhibition of primary cilia, use TRPV4 inhibitors or TRPV4 agonist, and use Immunofluorescence (IF), Immunohistochemistry (IHC), Western Blot (WB), Quantitative Real-time PCR (QP) to detect the expression of cartilage synthetic matrix and endoplasmic reticulum stress markers. The results revealed that LIPUS altered primary cilia expression, promoted synthetic matrix metabolism in articular chondrocytes and was associated with primary cilia. In addition, LIPUS exerted a active effect on OA by activating TRPV4, inducing calcium inward flow, and facilitating the entry of NF-κB into the nucleus to regulate synthetic matrix gene transcription. Inhibition of TRPV4 altered primary cilia expression in response to LIPUS stimulation, and knockdown of primary cilia similarly inhibited TRPV4 function. These results suggest that LIPUS mediates TRPV4 channels through primary cilia to regulate the process of knee osteoarthritis in mice.

Distributionally robust optimization for a capacity-sharing supply chain network design problem - Sha Niu; Gaoji Sun; Guoqing Yang (Journal of Cleaner Production, 2024)

The prolamins, from structure, property, to the function in encapsulation and delivery of bioactive compounds - Xinmei Sha; Haili Sun; Yue Li; Jincan Wu; Haotong Zhang; Rui Yang (Food Hydrocolloids, 2024)

Genome-wide identification and quantification of salinity-responsive Na+/K+-ATPase α-subunits in three salmonids - Yue Su; Shuang-En Yu; Yong-Xu Sun; Liang Zhang; Yue Tan; Yu-Yang Zhang; Shuo Wang; Yan-Gen Zhou; Li-Sha Hu; Yun-Wei Dong (Aquaculture, 2024)

Uptake and accumulation of di(2-ethylhexyl) phthalate (DEHP) in a soil-ginseng system and toxicological mechanisms on ginseng (Panax ginseng C.A. Meyer) - Yu-shun Lu; Zheng-bo Liu; Yan-yang Xu; Ji-yue Sha; Di Qu; Yin-shi Sun (Science of The Total Environment, 2024)

Natural and anthropogenic dissolved organic matter in landfill leachate: Composition, transformation, and their coexistence characteristics - Jing Zheng; Xian-Ge Wang; Yue Sun; Yu-Xin Wang; Hao-Qun Sha; Xiao-Song He; Xiao-Jie Sun (Journal of Hazardous Materials, 2024)

Paraprobiotic and postbiotic forms of Bacillus siamensis improved growth, immunity, liver and intestinal health in Lateolabrax maculatus fed soybean meal diet - Zi-Yan Liu; Hong-Ling Yang; Sha Li; Guo-He Cai; Ji-Dan Ye; Chun-Xiao Zhang; Yun-Zhang Sun (Fish & Shellfish Immunology, 2024)

Stay in touch with the endoplasmic reticulum - Sha Sun; Gan Zhao; Mingkang Jia; Qing Jiang; Shulin Li; Haibin Wang; Wenjing Li; Yunyun Wang; Xin Bian; Yan G. Zhao; Xun Huang; Ge Yang; et al. (Science China Life Sciences, 2024)

Deep electrical structures of Qinzhou-Fangcheng Junction Zone in Guangxi and seismogenic environment of the 1936 Lingshan M6¾ earthquake - Bin Zhou; Chunheng Yan; Yan Zhan; Xiangyu Sun; Sha Li; Xiang Wen; Yajun Mo; Yongdong Yuan; Yuan Yuan; Meili Huang (Science China Earth Sciences, 2024)

China's subtropical deciduous plants are more sensitive to climate change than evergreen plants by flowering phenology - Hong‐Li Li; Arshad Ali; Xu Luo; Ke Liao; Nan Sun; Ming‐Shan Xu; Long‐Bin Sha; Dong He; Yan‐Jun Du; Wei‐Wei Sun; Xiao‐Dong Yang (Global Change Biology, 2024)
The ongoing climate change‐induced shifts in flowering phenology have emerged as a consequential force impacting biodiversity and ecosystems. Despite the globally recognized significance of flowering phenology as a key reproductive attribute, studies in subtropical regions have been relatively fewer, particularly in comparison to temperate and cold regions. Additionally, the nuanced response of deciduous and evergreen plants to climate change remains insufficiently explored. In addressing this gap, we built a phenological model and a generalized linear mixed effect model to assess the differential responses of key flowering phenological traits, that is, first flowering date (FFD), peak flowering date (PFD), end of flowering date (EFD), and flowering duration (FD), to climate factors (temperature and precipitation) between deciduous and evergreen plants. We observed distinct responses in flowering phenological traits to climate change between deciduous and evergreen plants. Specifically, the advancement of FFD, PFD, and EFD in deciduous in response to temperature rise exceeded that in evergreen plants. FD in evergreen plants exhibited a stronger extension to temperature increase compared to deciduous. Conversely, the phenological change of evergreen plants in response to decreasing precipitation was greater than that of deciduous ones. Since temperature is a decisive climatic factor in affecting phenological changes, climate change‐induced advances in flowering phenology of deciduous plants are still larger than evergreen plants. Projections from our phenological model under future climate scenarios (SSP 1‐2.6 and SSP 5‐8.5) indicate a continuous enlargement of difference in flowering phenology between deciduous and evergreen plants, with this trend escalating into the future (2100>2070>2050>2030). The larger extension in FD of evergreens to climate change suggests a potential increase in their proportion within subtropical forest communities relative to deciduous plants. These insights contribute significantly to our understanding of the intricate dynamics of climate‐induced changes in subtropical plant ecosystems.

Effects of combined polystyrene nanoplastics and ibuprofen on the activated sludge processes: Short-term exposure in pure cultures versus long-term stress in mixed communities - Daying Chen; Mengxiao Li; Yang Li; Sha Long; Ximing Sun; Hongzhi Geng; Meilin Yin; Yongkui Yang; Lin Zhao (Journal of Water Process Engineering, 2024)

Surface sediment diatoms in the northern and middle Okinawa Trough and their correlation with environmental variables - Chipeng He; Bin Zhai; Tong Li; Zhilei Sun; Dongling Li; Xilin Zhang; Hao Xu; Xiaodong Yang; Longbin Sha (Journal of Asian Earth Sciences, 2024)

Biofortification of bok choy with selenium nanoparticles and its inhibitory effects on cadmium accumulation - Xuerong Di; Rui Jing; Sha Xie; Yuebing Sun; Qingqing Huang (Plant and Soil, 2024)

New record of the feather star Palaeocomatella hiwia (Echinodermata: Crinoidea: Comatulida) from Zhenbei Seamount in South China Sea: new insights into the taxonomic position of Palaeocomatella - Shao’e Sun; Zijie Mei; Zhongli Sha; Jing Wang; Nansheng Chen (Journal of Oceanology and Limnology, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Effects of five-year field aged zeolite on grain yield and reactive gaseous N losses in alternate wetting and drying paddy system - Qing Zhao; Taotao Chen; Shu Wang; Yan Sha; Feng Zhang; Yidi Sun; Daocai Chi (Science of The Total Environment, 2023)

Dietary supplementation with American ginseng dietary fiber ameliorates intestinal mucosal barrier injury in immunosuppressed mice - Jiyue Sha; Zhengbo Liu; Hongxia Yu; Xiaohui Huo; Jiajia Wang; Yuanyuan Duan; Wei Li; Di Qu; Zhiman Li; Jianbo Chen; Xueqing Li; Yinshi Sun (Food Bioscience, 2023)

Branch distribution pattern and anticoagulant activity of a fucosylated chondroitin sulfate from Phyllophorella kohkutiensis - Di Lan; Jiali Zhang; Xiaolei Shang; Lijuan Yu; Chen Xu; Pin Wang; Lige Cui; Nanqi Cheng; Huifang Sun; Jianing Ran; Le Sha; Ronghua Yin; et al. (Carbohydrate Polymers, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Understanding how microbial electrolysis cell assisted anaerobic digestion enhances triclocarban dechlorination in sludge - Sha Long; Qizi Fu; Zhixiang Hao; Luyang Sun; Zihan Li; Yike Guo; Xuran Liu; Fengming Song; Dongbo Wang; Wenming Wang (Chemical Engineering Journal, 2023)

Carrier-free 5-Fu nanoparticle-mediated domestication therapy for scar treatment: A preclinical and first-in-human study - Peng He; Sha Yi; Jianzhong Zhang; Chengchao Chu; Xuqi Peng; Changhong Li; Xinfei Sun; Yang Zhang; Hongwei Cheng; Xia Xiong; Gang Liu (Chemical Engineering Journal, 2023)

Research on the Multi-Equipment Cooperative Scheduling Method of Sea-Rail Automated Container Terminals under the Loading and Unloading Mode - Yongsheng Yang; Shu Sun; Sha He; Yajia Jiang; Xiaoming Wang; Hong Yin; Jin Zhu (Journal of Marine Science and Engineering, 2023)
A sea-rail automated container terminal (SRACT) plays a crucial role in the global logistics network, combining the benefits of sea and railway transportation. However, addressing the challenges of multi-equipment cooperative scheduling in terminal and railway operation areas is essential to ensure efficient container transportation. For the first time, this study addresses the cooperative scheduling challenges among railway gantry cranes, yard cranes, and automated guided vehicles (AGVs) under the loading and unloading mode in SRACTs, ensuring efficient container transportation. This requires the development of a practical scheduling model and algorithm. In this study, a mixed integer programming model was established for the first time to study the multi-equipment cooperative scheduling problem of a SRACT under the loading and unloading mode. A self-adaptive chaotic genetic algorithm was designed to solve the model, and the practicability and effectiveness of the model and algorithm were verified by simulation experiments. Furthermore, this study also proposes an AGV number adjustment strategy to accommodate changes in vessel arrival delays and train container types. Simulation experiments demonstrated that this strategy significantly reduces loading and unloading time, decreases equipment energy consumption, and improves the utilization rate of AGVs. This research provides valuable guidance for ongoing SRACT projects and advances and methodological approaches in multi-equipment co-operative scheduling for such terminals.

Surviving hot summer: Roles of phenotypic plasticity of intertidal mobile species considering microhabitat environmental heterogeneity - Yong-Xu Sun; Li-Sha Hu; Yun-Wei Dong (Journal of Thermal Biology, 2023)

Probiotic components of Bacillus siamensis LF4 mitigated β-conglycinin caused cell injury via modulating TLR2/MAPKs/NF-κB signaling in Lateolabrax maculatus - Zi-Yan Liu; Hong-Ling Yang; Sha Li; Guo-He Cai; Ji-Dan Ye; Chun-Xiao Zhang; Yun-Zhang Sun (Fish & Shellfish Immunology, 2023)

Dual network hydrogel coatings based on recombinant mussel protein with enhanced antibacterial and super-lubrication properties for urinary catheter applications - Yubo Hu; Youzhi Qiao; Peng Lei; Yian Gu; Liang Sun; Yibin Qiu; Sha Li; Hong Xu; Rui Wang (Chemical Engineering Journal, 2023)

Craniocervical Manual Lymphatic Drainage Increases the Efficiency of Atorvastatin-Based Treatment of Chronic Subdural Hematoma - Chuang Gao; Yingsheng Wei; Xinjie Zhang; Jinhao Huang; Meng Nie; Xuanhui Liu; Jiangyuan Yuan; Dong Wang; Ye Tian; Weiwei Jiang; Shuo An; Jian Sun; et al. (Translational Stroke Research, 2023)

Leachate leakage enhances the microbial diversity and richness but decreases Proteobacteria and weakens stable microbial ecosystem in landfill groundwater - Haoqun Sha; Zhenhai Liu; Yue Sun; Yuxin Wang; Xiange Wang; Jing Zheng; Yan Ma; Xiaosong He (Water Research, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Studying the effect of light intensity on the photosynthetic mechanism of pepper leaf yellowing mutants by proteomics and phosphoproteomics - Lianzhen Mao; Yunhua Dai; Yu Huang; Sha Yang; Hao Sun; Yao Zhou; Ying Sun; Bozhi Yang; Xuexiao Zou; Zhoubin Liu (Plant Science, 2023)

Structure, rheology, and antifreeze property of the exopolysaccharide from Naematelia aurantialba through basidiospore fermentation - Tao Sun; Xiaoyi Xu; Yuhang Ma; Hao jiang; Kai Yang; Rui Wang; Yian Gu; Sha Li; Yibin Qiu; Dafeng Sun; Hong Xu; Peng Lei (Food Hydrocolloids, 2023)

The biocontrol agent Bacillus velezensis T-5 changes the soil bacterial community composition by affecting the tomato root exudate profile - Yian Gu; Weina Liang; Zhidan Li; Sijie Liu; Sun Liang; Peng Lei; Rui Wang; Nan Gao; Sha Li; Zongqi Xu; Hong Xu (Plant and Soil, 2023)

Highly rearranged gene orders and rapid evolutionary rates in the mitochondrial genomes of Apodida (Echinodermata: Holothuroidea) - Shao’e Sun; Gang Ni; Wansheng Wang; Zhongli Sha; Ning Xiao; Zeng Xiaoqi (Frontiers in Marine Science, 2023)
Mitochondrial genome (mitogenome) is a frequently-used tool for phylogenetic and evolutionary studies among metazoans, however, it was still poorly represented in some invertebrate groups, including holothurians. Apodida is one of the most ancient orders of Holothuroidea, with unique characteristics in lacking tube feet and the respiratory tree. Here, we sequenced six mitogenomes from the holothurian order Apodida (Synaptidae and Chiridotidae) and compared them with other available holothurian mitogenomes. The apodan mitogenomes present positive GC skews and negative AT skews, a pattern diametrically opposite to that found in the mitogenomes of other holothurians. The amino acid genetic distances of the 13 protein-coding genes (PCGs) were the highest between Apodida and other holothurians. The mitochondrial gene orders within Apodida were extensively rearranged at the species level, and also were unique from the arrangement patterns of other holothurians. Phylogenetic relationships based on two different criteria: (i) nucleotides sequences with all codon positions (PCG 123 ) and (ii) Neutral Transitions Excluded model (NTE) confirmed the monophyly and basal position of the order Apodida with a long branch. The NTE phylogeny generated a low variation of branch length, but it did not ameliorate the long branch length of Apodida. The divergence time estimation suggested that the Apodida originated in the Middle Carboniferous, implying that they survived the extinction event that occurred in the boundary of the Permian and Triassic. The NTE dataset revealed younger age than that generated by PCG123 dataset. Apodida is accompanied by a faster evolutionary rate than other holothurians (0.0069 vs 0.0043 subs/s/my). The absence of tube feet and the respiratory tree may play an important role in the dramatic evolutionary changes of apodan mitogenomes.

Effects of thermal environment and air quality on outdoor thermal comfort in urban parks of Tianjin, China - Guangmeng Bian; Xiangyu Gao; Qishu Zou; Qi Cheng; Tianyi Sun; Shiyan Sha; Meng Zhen (Environmental Science and Pollution Research, 2023)

Surface chemistry regulation of nanoparticle coatings on activated carbons for rapid and long-lasting adsorption of organic pollutants - Xuan Jiao; Xingyu Liu; Yanzheng Ji; Sha Yang; Shu Yang; Pan Feng; Dewen Sun; Qianping Ran; Wei Liu; Xinquan Yu; Youfa Zhang (Journal of Cleaner Production, 2023)

CRISPR/Cas9-mediated BoaAOP2s editing alters aliphatic glucosinolate side-chain metabolic flux and increases the glucoraphanin content in Chinese kale - Hao Zheng; Wenli Huang; Xiangxiang Li; Huanhuan Huang; Qiao Yuan; Ruobin Liu; Hongmei Di; Sha Liang; Mengyu Wang; Mengyao Li; Zhi Huang; Yi Tang; et al. (Food Research International, 2023)

Aminopeptidase Play a Critical Role in the Accumulation of Free Amino Acids in Abalone (Haliotis discus hannai) During Cold Storage - Qiuying Ren; Yujia Wang; Sha Sun; Lingjing Zhang; Lechang Sun; Ling Weng; Guangming Liu; Minjie Cao (Journal of Ocean University of China, 2023)

Soil enzyme kinetics and thermodynamics in response to long-term vegetation succession - ZiWen Zhao; Yang Wu; WenJing Chen; Wei Sun; ZhanHui Wang; GuoBin Liu; Sha Xue (Science of The Total Environment, 2023)

Determination of minimum infusion rate of propofol in combination with electroacupuncture in goats - Lingling Liu; Mahmoud M. Abouelfetouh; Rui Sun; Eman Salah; Sha Nan; Mingxing Ding; Yuzhen Song; Yi Ding (Small Ruminant Research, 2023)

Late Eocene stepwise seawater retreat from the Pamir-Tian Shan convergence zone (Alay Valley) in the western Tarim Basin, China - Jimin Sun; Jingeng Sha; Brian F. Windley; Zhiliang Zhang; Bihong Fu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Integrative taxonomy reveals two new species of Lebbeus (Decapoda: Thoridae) from seamounts in NW Pacific, and questions the validity of the genus Paralebbeus - Yanrong Wang; Zhongli Sha; Shao'e Sun (Deep Sea Research Part I: Oceanographic Research Papers, 2023)

Cation-deficient T-Nb2O5/graphene Hybrids synthesized via chemical oxidative etching of MXene for advanced lithium-ion capacitors - Lei Wang; Xiong Zhang; Chen Li; Yanan Xu; Yabin An; Wenjie Liu; Tao Hu; Sha Yi; Kai Wang; Xianzhong Sun; Yue Gong; Zhong-Shuai Wu; et al. (Chemical Engineering Journal, 2023)

Raindrop size distribution and microphysical features of the extremely severe rainstorm on 20 July 2021 in Zhengzhou, China - Jianfang Ding; Wanshun Tian; Hui Xiao; Bo Cheng; Lei Liu; Xiuzhu Sha; Can Song; Yue Sun; Weixi Shu (Atmospheric Research, 2023)

Assessing decarbonization pathways of China’s heavy-duty trucks in a well-to-wheels perspective - Xingyu Xue; Jianxin Li; Xin Sun; Amir F. N. Abdul-Manan; Sha Du; Huanran Liu; Shujie Xu; Mingnan Zhao (The International Journal of Life Cycle Assessment, 2023)

Commensal Bacillus siamensis LF4 ameliorates β-conglycinin induced inflammation in intestinal epithelial cells of Lateolabrax maculatus - Zi-Yan Liu; Hong-Ling Yang; Xi-Yue Ding; Sha Li; Guo-He Cai; Ji-Dan Ye; Chun-Xiao Zhang; Yun-Zhang Sun (Fish & Shellfish Immunology, 2023)

Transportation decarbonization requires life cycle-based regulations: Evidence from China’s passenger vehicle sector - Xingyu Xue; Xin Sun; Hongrui Ma; Jianxin Li; Frank T. Hong; Sha Du (Transportation Research Part D: Transport and Environment, 2023)

Epigenetic reader MeCP2 repressed WIF1 boosts lung fibroblast proliferation, migration and pulmonary fibrosis - Ji-Ming Sha; Ren-Quan Zhang; Xian-Chen Wang; Yang Zhou; Kai Song; He Sun; Bin Tu; Hui Tao (Toxicology Letters, 2023)

Revisiting the role of firm-level carbon disclosure in sustainable development goals: Research agenda and policy implications - Beiling Ma; Sha Lin; Muhammad Farhan Bashir; Huaping Sun; Mahwish Zafar (Gondwana Research, 2023)

Rational design of molecular phototheranostic platform for NIR-II fluorescence imaging guided chemodynamic-photothermal combined therapy - Gui-long Wu; Bin Sun; Yuxuan He; Xiaofeng Tan; Qi Pan; Sha Yang; Na Li; Minghui Wang; Peixian Wu; Fen Liu; Hao Xiao; Li Tang; et al. (Chemical Engineering Journal, 2023)

Microplastic sink that cannot be ignored in chemosynthetic organisms - Kangning Zhang; Junhua Liang; Zhongli Sha; Li Zhou; Shan Zheng; Xiaoxia Sun (Marine Pollution Bulletin, 2023)

A temporospatial assessment of environmental quality in urbanizing Ethiopia - Jian Sun; Yang Hu; Yang Li; Lingfei Weng; Haonan Bai; Feidan Meng; Tao Wang; Huanzheng Du; Dong Xu; Sha Lu (Journal of Environmental Management, 2023)

Enhanced osmotic energy conversion through bacterial cellulose based double-network hydrogel with 3D interconnected nanochannels - Zhe Sun; Yudi Kuang; Mehraj Ahmad; Yang Huang; Sha Yin; Farzad Seidi; Sha Wang (Carbohydrate Polymers, 2023)

Research on the Cooperative Scheduling of ARMGs and AGVs in a Sea–Rail Automated Container Terminal under the Rail-in-Port Model - Yongsheng Yang; Sha He; Shu Sun (Journal of Marine Science and Engineering, 2023)
Reasonable scheduling of a train’s loading and unloading equipment can reduce the energy consumption of production operations; this has great value for the green development of terminals. The collaborative scheduling model of the Automated Rail Mounted Gantry (ARMG) and Automated Guided Vehicle (AGV) is used to minimize the energy consumption of equipment in a scenario of a vertical railway entering a port and a shared storage yard existing between the port and railway under the mixed operation mode of “train–ship” and “train–yard–ship”. According to the characteristics of the model, the two-layer scheduling rule and the self-adaptive chaos genetic algorithm (SCGA) were proposed to solve the problem of placing the ARMG and the AGV on the same schedule. Simulation experiments verified the effectiveness of the model and algorithm. The effects of the delayed arrival of vessels, the proportion of “transshipment” containers, and the number of automated ARMGs and AGVs on total energy consumption were analyzed. The results showed that when all containers are “train–ship” containers, the number of ARMG and AGV at 1:4 will minimize the total operational energy consumption. Furthermore, as ships take longer to arrive, reducing the number of AGVs can cut energy use by 15% for the same number of ARMG.

Which strategy among avoid, shift, or improve is the best to reduce CO2 emissions from sand and gravel aggregate transportation? - Yuting Zhu; Hao Ma; Chuan Sha; Yang Yang; Haijiao Sun; Feifei Ming (Journal of Cleaner Production, 2023)

Designing direct redox reaction chemically coupling NO and SO2 removal - Dongyue Zhao; Qiuqiao Jiang; Bo Peng; Jun Liu; Ruoyu Wang; Menglong Feng; Shangcong Sun; Hao Sha; Kai Zhu; Haitao Song; Wei Lin; Zhijian Da (Fuel, 2023)

Quality assessment of variable collagen tissues of sea cucumber (Stichopus japonicus) body wall under different heat treatment durations by label-Free proteomics analysis - Yi-Zhen Huang; Yi-Sha Xie; Yan-Xin Li; Mei-Yu Zhao; Na Sun; Hang Qi; Xiu-Ping Dong (Food Research International, 2023)

Divergent evolution of mitogenomics in Cetartiodactyla niche adaptation - Xibao Wang; Yongquan Shang; Xiaoyang Wu; Qinguo Wei; Shengyang Zhou; Guolei Sun; Xuesong Mei; Yuehuan Dong; Weilai Sha; Honghai Zhang (Organisms Diversity & Evolution, 2023)

A self-circulating electro-fenton-like process over Fe3O4–CaO2 cathode for highly efficient degradation of levofloxacin - Yangyang Bai; Xiaoqin Sun; Yuan Dang; Sha Yu; Jun-Jie Zhu; Yuanzhen Zhou (Chemosphere, 2023)

Maternal exposure to 4-vinylcyclohexene diepoxide during pregnancy induces subfertility and birth defects of offspring in mice - Wei Song; Ang Li; Qian-Qian Sha; Shao-Yuan Liu; Yong Zhou; Chang-Yin Zhou; Xue Zhang; Xiao-Zhen Li; Jia-Xin Jiang; Fei Li; Chao Li; Heide Schatten; et al. (Science of The Total Environment, 2023)

Leverage of resource efficiency over environmental emissions: Case of a megacity in China - Jian Sun; Tao Wang; Sha Lu; Xiaofeng Gao; Huanzheng Du (Science of The Total Environment, 2023)

Design and synthesis of SO3H-functionalized acidic ionic liquids for catalytic conversion of wheat straw to ethyl levulinate - Chao Li; Jian Zhao; Huixin Tong; Xiaodong Fan; Xinjie Fang; Yuli Sha; Zhizhong Sun; Wenyi Chu (Fuel, 2023)

Secondary vegetation succession on the Loess Plateau altered the interaction between arbuscular mycorrhizal fungi and nitrogen-fixing bacteria - Meng Liang; Yang Wu; Qifan Zhao; Yaokun Jiang; Wei Sun; Guobin Liu; Lihui Ma; Sha Xue (Forest Ecology and Management, 2023)

Magnetic hydrothermal carbonaceous nanospheres bonded cell membranes as a stable and reusable platform for discovering natural bioactive components - Sha Liu; Pingyu Ye; Zhenqi Sang; Wan Gong; Peng Sun; Shan Tao; Qiaoyan Zhang; Lupin Qin; Qiming Zhao (Chemical Engineering Journal, 2023)

Isolation, characterization and functional validation of a soybean transcription factor, GmDof4.2 improves drought tolerance in transgenic tobacco - Ying Zhai; Jiongxin Chen; Jiaqi He; Jun Zhang; Wei Sha; Haiwei Yu; Yan Zhao; Tianyi Ma; Tianguo Sun; Meijuan Zhang; Shanshan Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Evaluation of data pre-processing and regression models for precise estimation of soil organic carbon using Vis–NIR spectroscopy - Yaxin Wang; Sha Yang; Xiaobin Yan; Chenbo Yang; Meichen Feng; Lujie Xiao; Xiaoyan Song; Meijun Zhang; Fahad Shafiq; Hui Sun; Guangxin Li; Wude Yang; et al. (Journal of Soils and Sediments, 2023)

Combined effect of Cu- and ZnO- NPs on antibiotic resistance genes in an estuarine water - Yu-ru Chen; Rong-rong Sha; Xiao-li Sun; Xing-pan Guo; Yi Yang (Frontiers in Marine Science, 2023)
Most studies of whether and how nanoparticles (NPs) affect antibiotic resistance genes (ARGs) focus on testing single NPs type. In this study, we determined the combined effect of Cu- and ZnO- NPs in the water samples collected from the Yangtze River Estuary and found the effect differs greatly from that produced by individual NPs. The results showed that the Cu- and ZnO- NPs co-exposure resulted in an enrichment of ARGs, whereas individual Cu- and ZnO- NPs exposure decreased the abundance of ARGs. Furthermore, the co-exposure of Cu- and ZnO- NPs induced obvious changes in the microbial communities compared to the control communities. Redundancy analysis suggested that the microbial community contributed the most (43.5%) to the ARG profiles, followed by dissolved metal ions (25.7%), MRGs, (19.4%), and MGEs (4.4%). Network analysis found several potential hosts (such as Mycobacterium and Escherichia coli ) and implied the extent of the risk of ARG transmission into various environmental niches by these common microbes.

Iron-calcium reinforced solidification of arsenic alkali residue in geopolymer composite: Wide pH stabilization and its mechanism - Yingfei Sun; Pan Zhang; Zhen Li; Jing Chen; Yan Ke; Jingping Hu; Bingchuan Liu; Jiakuan Yang; Sha Liang; Xintai Su; Huijie Hou (Chemosphere, 2023)

Study on sex-linked region and sex determination candidate gene using a high-quality genome assembly in yellow drum - Sha Sun; Chaowei Song; Fang Han; Qiwei He; Jieping Liu; Sen Zhang; Wei Han; Kun Ye; Zhaofang Han; Zhiyong Wang; Wanbo Li (Aquaculture, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

All-Ceramic, compressible and scalable nanofibrous aerogels for subambient daytime radiative cooling - Tao Li; Haoyang Sun; Meng Yang; Chentao Zhang; Sha Lv; Bin Li; Longhao Chen; Dazhi Sun (Chemical Engineering Journal, 2023)

Mitogenomes provide insights into the phylogeny and evolution of brittle stars (Echinodermata, Ophiuroidea) - Shao'e Sun; Ning Xiao; Zhongli Sha (Zoologica Scripta, 2023)
Ophiuroidea is the most speciose of all classes of Echinoderma. It is an important component in benthic ecosystems, occurring in almost all ecological niches of modern seas. To date, the phylogeny and complete evolutionary history of the ophiuroids have not yet been fully resolved. In this study, we sequenced the complete mitochondrial genomes (mitogenomes) of Ophiothrix ( Ophiothrix ) exigua and two deep‐sea species Histampica sp. CS049 and Ophioplinthaca sp. M5261. These two deep‐sea ophiuroids displayed reversed strand‐compositional bias and rearranged gene orders. Thirteen distinct patterns of mitochondrial gene order among ophiuroid mitogenomes were detected, with two gene order newly found in Ophiuroidea. Our data supported the gene order found in all sampled Ophiuridae as the most likely ancestral order of all Ophiuroidea. To improve phylogenetic accuracy based on nucleotide differences, two different criteria were used for the analyses: (i) nucleotide sequence from all codon positions (PCG 123 ); (ii) the NTE method (“Neutral Transitions Excluded”) for ameliorating the misleading effects of a reverse strand bias in the data. The two methods confirmed the polyphyly of the orders Ophiacanthida and Amphilepidia. At family and genus level, Ophiuridae, Ophionotus and Ophioplinthus were not monophyletic. The most notable exception was that the NTE phylogeny showed low variation of branch length. NTE dataset generated younger age for most lower‐level nodes than that from PCG123 dataset. All analyses suggested that the ophiuroids radiation occurred around the Permian–Triassic mass extinction event, and the divergence time of the deep‐sea lineages was during the Cretaceous.

Correction to: Can China’s carbon trading policy improve the profitability of polluting firms: a retest of Porter’s hypothesis - Xiaosong Ren; Qian Ma; Sha Sun; Xiaohang Ren; Guang Yan (Environmental Science and Pollution Research, 2022)

Three new species and two new records of Echinothuriidae (Echinodermata: Echinothurioida) from seamounts in the Northwest Pacific Ocean: Diversity, phylogeny and biogeography of deep-sea echinothuriids - Wanrui Zheng; Shao’e Sun; Zhongli Sha; Ning Xiao (Frontiers in Marine Science, 2022)
The soft sea urchins Echinothuriidae Thomson, 1872, constitute the most commonly encountered sea urchins in the bathyal environment. The echinothuriids are common and frequently abundant in the Indo-Pacific, but the species diversity is still not completely known yet. Our examination of echinoid specimens collected from seven seamounts in the Northwest Pacific Ocean revealed three new species and two new records. The three new species are described as Araeosoma cucullatum sp. nov., Araeosoma polyporum sp. nov., and Hygrosoma involucrum sp. nov. The two new records included two species from the genus Araeosoma . They are distinguished from each other and from congeners by the following characteristics: coloring, ambulacrum, interambulacrum, apical system, spines, and pedicellariae. The identities of the five species are well supported by genetic distance and phylogenetic analyses based on the mitochondrial cytochrome oxidase subunit I ( COI ) and 16S rRNA genes. Based on the distribution data, we explored the distribution patterns of Araeosoma , Calveriosoma , Hapalosoma , Sperosoma , Tromikosoma , and Hygrosoma , the six echinothuriid genera occurring in deep sea, and delineated 10 isolated deep-sea biogeographic provinces all over the world. The Western Pacific harbors higher species diversity of deep-sea echinothuriids than other sea areas worldwide, indicating that the Western Pacific may play an important part in the dispersal and speciation of deep-sea echinothuriids.

Can China’s carbon trading policy improve the profitability of polluting firms: a retest of Porter’s hypothesis - Xiaosong Ren; Qian Ma; Sha Sun; Xiaohang Ren; Guang Yan (Environmental Science and Pollution Research, 2022)

Reconstitution of Fusion-Competent Human Placental Fusogen Syncytin-2 - Lu Xu; Sha Sun (The Journal of Membrane Biology, 2022)

Network pharmacological investigation into the mechanism of Kaixinsan powder for the treatment of depression - Li-Jing Du; Xin-Ning Zhang; Sha-Sha Li; Yuan-Fang Sun; Hui-Zi Jin; Shi-Kai Yan; Chuan-Gang Han (Metabolic Brain Disease, 2022)

The role of ancestral seascape discontinuity and geographical distance in structuring rockfish populations in the Pacific Northwest - Cheng-He Sun; Rodolphe Elie Gozlan; Ting Wu; Dan Xue; Ye-Ling Lao; Jian-Feng Yu; Xiao-Shu Zeng; Sha Li; Emilie A. Hardouin; Demetra Andreou; Qun Zhang (Frontiers in Marine Science, 2022)
Despite the apparent absence of physical barriers in the ocean to prevent dispersal, recent studies have highlighted the importance of biological, geographical, physical, and historical barriers in the genetic structuring of marine species populations. This representation is essential for the sustainable exploitation of natural marine resources and for the setup of efficient protected area networks for the conservation of marine species. In this study, we used extensive sampling of Sebastiscus marmoratus , a commercially important inshore rockfish with high site fidelity, to characterize their population genetic structure along the China–Japan coast and to determine the effect of past geological and current biological–physical barriers on the current genetic footprint. A 461-bp fragment of the mtDNA hypervariable portion control region was sequenced for 675 individuals from 15 geographical locations. A total of 292 haplotypes were identified. The population of S. marmoratus showed high haplotype and nucleotide diversity. Pairwise fixation index ( F ST ) and analysis of molecular variance (AMOVA) revealed significant genetic differentiation among populations. The Bayesian skyline plots and neutrality statistics showed a sudden expansion of the S. marmoratus population around the Pleistocene. The Beibu Gulf group had the lowest mean number of pairwise differences, the lowest significant genetic differentiation, and the lowest haplotype and nucleotide diversity, and should be prioritized for protection in the future. Ocean currents, seascape discontinuity, geographical distance, and ecological characteristics may play an important role in shaping the contemporary phylogeographical patterns and population structures of S. marmoratus .

Vasorin contributes to lung injury via FABP4-mediated inflammation - Xiaoping Guo; Junming Sun; Jinning Liang; Siran Zhu; Mingyuan Zhang; Lichao Yang; Xuejing Huang; Kangning Xue; Zhongxiang Mo; Sha Wen; Bing Hu; Jiajuan Liu; et al. (Molecular Biology Reports, 2022)

ML323, a USP1 inhibitor triggers cell cycle arrest, apoptosis and autophagy in esophageal squamous cell carcinoma cells - Yaxin Sun; Beibei Sha; Wenjing Huang; Miaomiao Li; Shan Zhao; Yuan Zhang; Jie Yan; Zheng Li; Jingwen Tang; Peiyan Duan; Jianxiang Shi; Pei Li; et al. (Apoptosis, 2022)

Generating phone-quality records to train machine learning models for smartphone-based earthquake early warning - Zengwei Zheng; Jiquan Wang; Lifei Shi; Sha Zhao; Jianmin Hou; Lin Sun; Lin Dong (Journal of Seismology, 2022)

A Shuttling Protein Kank1 Plays Important Role in the Sex Determination in Yellow Drum - Sha Sun; Jieping Liu; Sen Zhang; Qiwei He; Wei Han; Kun Ye; Fang Han; Wanbo Li; Zhiyong Wang (Frontiers in Marine Science, 2022)
Sex is one of the most important scientific topics, and the existence of sex dimorphism is a conserved feature in vertebrate taxa. The research on sex-determining genes and sex chromosome evolution is a hot topic in biology. The majority of sex-determining genes expressed in somatic cells, and reciprocal interactions between germ cells and somatic cells, are important for gonadal differentiation. However, the knowledge of how signals are transmitted between somatic cells and germ cells remains unclear. In this study, we confirmed the 36 dph was a sex determination critical stage in yellow drum through transcriptome analysis at the early development stages. We further found that Kank1 participated in the germ cells’ motility process in yellow drum through KEGG pathway analysis together with protein-protein interaction network. With the dual-luciferase reporter assay, we detected that Kank1 increased the transcription of dmrt1_Luc gene in CHO cells and 293T cells. Additionally, we observed that Kank1 was not only expressed in the cytoplasm but also in the nucleus in CHO cells through a fluorescence microscope. These results suggest that Kank1 acts as a shuttling protein as in humans and may play a difunctional role at the early gonad development stage in yellow drum, and it not only participated in the germ cells’ motility but also increased the expression of dmrt1 in yellow drum.

Genome-wide identification of quantitative trait loci for morpho-agronomic and yield-related traits in foxtail millet (Setaria italica) across multi-environments - Tianpeng Liu; Jihong He; Kongjun Dong; Xuewen Wang; Lei Zhang; Ruiyu Ren; Sha Huang; Xiaoting Sun; Wanxiang Pan; Wenwen Wang; Peng Yang; Tianyu Yang; et al. (Molecular Genetics and Genomics, 2022)
Foxtail millet ( Setaria italica ) is an ideal model of genetic system for functional genomics of the Panicoideae crop. Identification of QTL responsible for morpho-agronomic and yield-related traits facilitates dissection of genetic control and breeding in cereal crops. Here, based on a Yugu1 × Longgu7 RIL population and genome-wide resequencing data, an updated linkage map harboring 2297 bin and 74 SSR markers was constructed, spanning 1315.1 cM with an average distance of 0.56 cM between adjacent markers. A total of 221 QTL for 17 morpho-agronomic and yield-related traits explaining 5.5 ~ 36% of phenotypic variation were identified across multi-environments. Of these, 109 QTL were detected in two to nine environments, including the most stable qLMS6.1 harboring a promising candidate gene Seita.6G250500 , of which 70 were repeatedly identified in different trials in the same geographic location, suggesting that foxtail millet has more identical genetic modules under the similar ecological environment. One hundred-thirty QTL with overlapping intervals formed 22 QTL clusters. Furthermore, six superior recombinant inbred lines, RIL35, RIL48, RIL77, RIL80, RIL115 and RIL125 with transgressive inheritance and enrichment of favorable alleles in plant height, tiller, panicle morphology and yield related-traits were screened by hierarchical cluster. These identified QTL, QTL clusters and superior lines lay ground for further gene-trait association studies and breeding practice in foxtail millet.

Mitogenomes Provide Insights Into the Evolution of Thoracotremata (Brachyura: Eubrachyura) - Shao’e Sun; Wei Jiang; Ziming Yuan; Zhongli Sha (Frontiers in Marine Science, 2022)
Thoracotremata is a group of Brachyura, with 1,248 extant species. To date, parts of the thoracotreme phylogeny are not yet resolved and require further investigation . In this study, 12 new mitogenomes from the four thoracotreme superfamilies were sequenced. They contain a standard set of 37 genes, and vary in size from 15,422 ( Hapalocarcinus marsupialis Stimpson, 1858 sensu lato ) to 16,490 bp [ Arcotheres sinensis (Shen, 1932)]. Combined with 58 thoracotreme mitochondrial genomes (mitogenomes) from GenBank, we described the evolution of gene rearrangement and the internal phylogenetic relationships of Thoracotremata, and evaluated the phylogenetic position of Cryptochiroidea and Pinnotheroidea. Nine distinct patterns of mitochondrial gene order (MGO) among thoracotreme mitogenomes are identified, with four MGOs newly found in Thoracotremata. All other gene orders are the result of transformational pathways originating from brachyuran gene order (BraGO). The different gene orders have variable levels of gene rearrangements, which involve both tRNAs and protein-coding genes. No link between variable gene arrangements (breakpoint distances) and nucleotide substitution rates (branch lengths) is found in thoracotreme crabs. The symbiotic groups, the cryptochiroid and pinnotheroid crabs, display variable MGOs (CryGO, Pin1GO, and Pin2GO), providing evidence for possible correlations of rearranged MGOs to the adaptations to specialized lifestyles. In our phylogenetic analyses, Cryptochiridae (Cryptochiroidea) show close relationship with an Ocypodoidea lineage (Camptandriidae/Xenophthalmidae/Dotillidae). Pinnotheridae (Pinnotheroidea) form the basal monophyletic clade.

Activating PIK3CA postzygotic mutations in segmental overgrowth of muscles with bone involvement in the body extremities - Wen Tian; Liying Sun; Qi Zhang; Junhui Zhao; Yang Guo; Wenyao Zhong; Liu Liu; Katia Meirelles; Sha Tang; Jing Zhang; Yingzhao Huang; Yuehan Yin; et al. (Molecular Genetics and Genomics, 2022)

Biogeography of culturable marine bacteria from both poles reveals that ‘everything is not everywhere’ at the genomic level - Qi‐Long Qin; Zhi‐Bin Wang; Qian‐Qian Cha; Sha‐Sha Liu; Xue‐Bing Ren; Hui‐Hui Fu; Mei‐Ling Sun; Dian‐Li Zhao; Andrew McMinn; Yin Chen; Xiu‐Lan Chen; Yu‐Zhong Zhang; et al. (Environmental Microbiology, 2022)
Summary Based on 16S rRNA gene analyses, the same bacterial operational taxonomic units (OTUs) are common to both the Arctic and Antarctic oceans, supporting the concept ‘everything is everywhere’. However, whether the same OTUs from both poles have identical genomes, i.e. whether ‘everything is still everywhere’ at the genomic level has not yet been examined systematically. Here, we isolated, sequenced and compared the genomes of 45 culturable marine bacteria belonging to three genera of Salinibacterium , Psychrobacter and Pseudoalteromonas from both polar oceans. The bacterial strains with identical 16S rRNA genes were common to both poles in every genus, and four identical genomes were detected in the genus Salinibacterium from the Arctic region. However, no identical genomes were observed from opposite poles in this study. Our data, therefore, suggest that ‘everything is not everywhere’ at the genomic level. The divergence time between bacteria is hypothesized to exert a strong impact on the bacterial biogeography at the genomic level. The geographical isolation between poles was observed for recently diverged, highly similar genomes, but not for moderately similar genomes. This study thus improves our understanding of the factors affecting the genomic‐level biogeography of marine microorganisms isolated from distant locations.

Hydrogen Sulfide Maintains Good Nutrition and Delays Postharvest Senescence in Postharvest Tomato Fruits by Regulating Antioxidative Metabolism - Ting-Ying Zhong; Gai-Fang Yao; Sha-Sha Wang; Ting-Ting Li; Ke-Ke Sun; Jun Tang; Zhong-Qin Huang; Feng Yang; Yan-Hong Li; Xiao-Yan Chen; Lan-Ying Hu; Hua Zhang; et al. (Journal of Plant Growth Regulation, 2021)

Types, characteristics, distribution, and genesis of pockmarks in the South China Sea: insights from high-resolution multibeam bathymetric and multichannel seismic data - Song Zhu; Xuejie Li; Huodai Zhang; Zhibin Sha; Zhen Sun (International Geology Review, 2021)

Mitochondrial phylogenomics reveal the origin and adaptive evolution of the deep-sea caridean shrimps (Decapoda: Caridea) - Shao’e Sun; Zhongli Sha; Yanrong Wang (Journal of Oceanology and Limnology, 2021)

Screening and isolation of glyceroglycolipids with antialgal activity from several marine macroalgae - Ying-Ying Sun; Sha-Sha Dong; Nai-Sheng Zhang; Jing Zhou; Zheng-Kang Long (Journal of Applied Phycology, 2021)

Observational study of land-atmosphere turbulent flux exchange over complex underlying surfaces in urban and suburban areas - Jie Sha; Jun Zou; Jianning Sun (Science China Earth Sciences, 2021)

Cellulomonas taurus sp. nov., a novel bacteria with multiple hydrolase activity isolated from livestock, and potential application in wastewater treatment - Sha-Sha Zhang; Jian-Feng Xu; Xiao-LI Sun; Wei Guo; Zeng-Shan Liu (Antonie van Leeuwenhoek, 2021)

The pore characteristics and its geochemical and mineralogical controls of marine-continental transitional shales from Keluke Formation in the Qaidam Basin, Northwest China - Sha-sha Sun; Jie Dai; Hui Han; Peng Pang; Chen Guo; Zhen-gang Ding; Yuan Gao (Arabian Journal of Geosciences, 2021)

Formation of cadmium sulfide nanoparticles mediates cadmium resistance and light utilization of the deep‐sea bacterium Idiomarina sp. OT37 ‐5b - Ning Ma; Zhongli Sha; Chaomin Sun (Environmental Microbiology, 2021)
Summary Heavy metal is one of the major factors threatening the survival of microorganisms. Here, a deep‐sea bacterium designated Idiomarina sp. OT37‐5b possessing strong cadmium (Cd) tolerance was isolated from a typical hydrothermal vent. Both the Cd‐resistance and removal efficiency of Idiomarina sp. OT37‐5b were significantly promoted by the supplement of cysteine and meanwhile large amount of CdS nanoparticles were observed. Production of H 2 S from cysteine catalysed by methionine gamma‐lyase was further demonstrated to contribute to the formation of CdS nanoparticles. Proteomic results showed the addition of cysteine effectively enhanced the efflux of Cd, improved the activities of reactive oxygen species scavenging enzymes, and thereby boosted the nitrogen reduction and energy production of Idiomarina sp. OT37‐5b. Notably, the existence of CdS nanoparticles obviously promoted the growth of Idiomarina sp. OT37‐5b when exposed to light, indicating this bacterium might grab light energy through CdS nanoparticles. Proteomic analysis revealed the expression levels of essential components for light utilization including electron transport, cytochrome complex and F‐type ATPase were significantly up‐regulated, which strongly suggested the formation of CdS nanoparticles promoted light utilization and energy production. Our results provide a good model to investigate the uncovered mechanisms of self‐photosensitization of nonphotosynthetic bacteria for light‐to‐chemical production in the deep biosphere.

Carbon material–immobilized ionic liquids were applied on absorption of Hg2+ from water phase - Lihan Sun; Mengru Wang; Wei Li; Sha Luo; Yan Wu; Chunhui Ma; Shouxin Liu (Environmental Science and Pollution Research, 2020)

Inhibition of glycolysis ameliorate arthritis in adjuvant arthritis rats by inhibiting synoviocyte activation through AMPK/NF-кB pathway - Ying Wang; Hao Xian; Jiajia Qi; Fang Wei; Xiu Cheng; Sha Li; Qing Wang; Zhaoyang Liu; Yun Yu; Jing Zhou; Xiaojin Sun; Hao Liu; et al. (Inflammation Research, 2020)

Complete mitochondrial genomes of two deep-sea pandalid shrimps, Heterocarpus ensifer and Bitias brevis: insights into the phylogenetic position of Pandalidae (Decapoda: Caridea) - Shao’e Sun; Jiao Cheng; Song Sun; Zhongli Sha (Journal of Oceanology and Limnology, 2020)

Energy transition, CO2 mitigation, and air pollutant emission reduction: scenario analysis from IPAC model - Kejun Jiang; Sha Chen; Chenmin He; Jia Liu; Sun Kuo; Li Hong; Songli Zhu; Xiang Pianpian (Natural Hazards, 2019)

Functional characterization of three MATE genes in relation to aluminum-induced citrate efflux from soybean root - Ying Zhou; Zhengbiao Wang; Li Gong; Anle Chen; Ning Liu; Sha Li; Haoran Sun; Zhenming Yang; Jiangfeng You (Plant and Soil, 2019)

The associations of air pollution exposure during pregnancy with fetal growth and anthropometric measurements at birth: a systematic review and meta-analysis - Li Fu; Yi Chen; Xinyi Yang; Zuyao Yang; Sha Liu; Lei Pei; Baixiang Feng; Ganxiang Cao; Xin Liu; Hualiang Lin; Xing Li; Yufeng Ye; et al. (Environmental Science and Pollution Research, 2019)

Neurons in rat orbitofrontal cortex and medial prefrontal cortex exhibit distinct responses in reward and strategy-update in a risk-based decision-making task - Dan-Dan Hong; Wen-Qiang Huang; Ai-Ai Ji; Sha-Sha Yang; Hui Xu; Ke-Yi Sun; Aihua Cao; Wen-Jun Gao; Ning Zhou; Ping Yu (Metabolic Brain Disease, 2019)

Betulinic acid attenuates liver fibrosis by inducing autophagy via the mitogen-activated protein kinase/extracellular signal-regulated kinase pathway - Yuan Liu; Yanmeng Bi; Chan Mo; Ting Zeng; Sha Huang; Lei Gao; Xuegang Sun; Zhiping Lv (Journal of Natural Medicines, 2019)

Mitochondrial phylogenomics reveals insights into taxonomy and evolution of Penaeoidea (Crustacea: Decapoda) - Jiao Cheng; Tin‐Yam Chan; Nan Zhang; Song Sun; Zhong‐li Sha (Zoologica Scripta, 2018)
The taxonomy and phylogeny of Penaeoidea have long been fraught with controversy. Here, we carried out the first mitochondrial phylogenomic analysis on all the penaeoid families and tribes, including nine newly sequenced and 14 published mitogenomes, towards elucidating the phylogeny and evolutionary history of Penaeoidea. All these nine mitogenomes exhibit the pancrustacean ground pattern, except that Benthonectes filipes contains two additional clusters of tRNA Ala , tRNA Arg and tRNA Asn and an uncommon noncoding region. The resulted phylogenetic tree is generally well resolved with Benthesicymidae sister to Aristeidae, forming a clade with Solenoceridae. Contrary to traditional classification, this clade has a sister relationship with the tribe Penaeini of the family Penaeidae. The family Sicyoniidae is deeply nested within the penaeid tribe Trachypenaeini which forms a sister clade with the remaining penaeid tribe, Parapenaeini. As the family Penaeidae is recovered to be polyphyletic, the three tribes in Penaeidae are all elevated to familial status. On the other hand, the family Sicyoniidae is retained to accommodate Trachypenaeini because they are now synonyms and the former name is more senior. This work is the first molecular analysis concurring with the latest findings in fossil assessments showing that Parapeaneini is the most primitive in Penaeoidae. Our results also illustrate a shallow‐water origin and an onshore–offshore evolutionary shift in penaeoid shrimps.

Variability in zonal location of winter East Asian jet stream - Sha Wu; Jianqi Sun (International Journal of Climatology, 2017)
This study reveals that the winter East Asian jet stream ( EAJS ) shows a strong variability in its zonal location; this topic has received less attention compared with the EAJS intensity and meridional location variability in previous studies. We show that the mid‐to‐high latitude climate system is mainly responsible for the EAJS eastward shift and the tropical system is closely related with the EAJS westward shift. In the EAJS east‐located years, North Pacific Oscillation undergoes a positive phase, which can enhance the eastern part of the EAJS over the North Pacific, favouring the eastward shift of the EAJS . In the west‐located years, the tropical convection over the Indian Ocean is strong, which can strengthen the zonal angular momentum transport from the Tropics to subtropical westerly belt. Consequently, the western part of the EAJS enhances and the EAJS shifts westward. In addition, the east‐located EAJS is related to the intensified Aleutian Low and East Asian trough, and thus, Northeast China, Korean Peninsula, and Japan experience low temperatures. On the other hand, the west‐located EAJS is associated with the weakened mid‐Asian ridge and cold‐temperature advection over southern East Asia, and thus, regions from mid‐Asia southeastward to southern China experience cold temperatures. Therefore, the zonal location of the EAJS is a potentially good index of the northern or southern East Asian anomalous temperature pattern.

An optical material for the detection of trace S2O3 2− in milk based on a copper complex - Qingming Wang; Huifang Sun; Weilin Sha; Juan Chen; Liuyue Gu; Dong Wang; Xinhui Tang (BioMetals, 2017)

Reversible Absorption and Emission Responses of Nile Blue and Azure A Derivatives in Extreme Acidic and Basic Conditions - Xiu-Li Wang; Ru Sun; Wei-Jin Zhu; Xin-Long Sha; Jian-Feng Ge (Journal of Fluorescence, 2017)

Effects of γ-Aminobutyric Acid, Glutamic Acid, and Calcium Chloride on Rice (Oryza sativa L.) Under Cold Stress During the Early Vegetative Stage - Yan Jia; Detang Zou; Jingguo Wang; Hanjing Sha; Hualong Liu; Mallano Ali Inayat; Jian Sun; Hongliang Zheng; Nan Xia; Hongwei Zhao (Journal of Plant Growth Regulation, 2017)

Deletion of mTOR in Reactive Astrocytes Suppresses Chronic Seizures in a Mouse Model of Temporal Lobe Epilepsy - Xueqin Wang; Longze Sha; Nannan Sun; Yan Shen; Qi Xu (Molecular Neurobiology, 2017)

The Role of Nitric Oxide and Sympathetic Control in Cerebral Autoregulation in the Setting of Subarachnoid Hemorrhage and Traumatic Brain Injury - Zhen-Ni Guo; Anwen Shao; Lu-Sha Tong; Weiyi Sun; Jia Liu; Yi Yang (Molecular Neurobiology, 2016)

Adenylate kinase: a novel antigen for immunodiagnosis and subunit vaccine against tuberculosis - Yangjiong Xiao; Wei Sha; Zhaofeng Tian; Yingying Chen; Ping Ji; Qin Sun; Huiyu Wang; Shujun Wang; Yong Fang; Han-Li Wen; Hui-min Zhao; Jie Lu; et al. (Journal of Molecular Medicine, 2016)

The association between the ring finger protein 213 (RNF213) polymorphisms and moyamoya disease susceptibility: a meta-analysis based on case–control studies - Xun-Sha Sun; Jun Wen; Jiao-Xing Li; Rong Lai; Yu-Fang Wang; Hui-Jiao Liu; Wen-Li Sheng (Molecular Genetics and Genomics, 2016)

Role of the North Pacific sea surface temperature in the East Asian winter monsoon decadal variability - Jianqi Sun; Sha Wu; Juan Ao (Climate Dynamics, 2016)

Microsatellite records for volume 8, issue 2 - Dareen Almojil; Maria Cristina Arias; Rochelle R. Beasley; Yiyong Chen; Rulon W. Clark; Yinghui Dong; Zhiguo Dong; Natalie Forsdick; Elaine Françoso; E. González-Ortegón; A. M. González-Tizón; Linsheng Gui; et al. (Conservation Genetics Resources, 2016)

Dissection of QTL alleles for blast resistance based on linkage and linkage disequilibrium mapping in japonica rice seedlings - Liying Guo; Hongwei Zhao; Jingguo Wang; Hualong Liu; Hongliang Zheng; Jian Sun; Luomiao Yang; Hanjing Sha; Detang Zou (Australasian Plant Pathology, 2016)

Hypermethylation of Hippocampal Synaptic Plasticity-Related genes is Involved in Neonatal Sevoflurane Exposure-Induced Cognitive Impairments in Rats - Ling-sha Ju; Min Jia; Jie Sun; Xiao-ru Sun; Hui Zhang; Mu-huo Ji; Jian-jun Yang; Zhong-yun Wang (Neurotoxicity Research, 2016)

Environmental Enrichment Ameliorates Neonatal Sevoflurane Exposure-Induced Cognitive and Synaptic Plasticity Impairments - Mu-huo Ji; Xing-ming Wang; Xiao-ru Sun; Hui Zhang; Ling-sha Ju; Li-li Qiu; Jiao-jiao Yang; Min Jia; Jing Wu; Jianjun Yang (Journal of Molecular Neuroscience, 2015)

Relative contributions of spatial and environmental processes and biotic interactions in a soil collembolan community - Di Sha; Meixiang Gao; Xin Sun; Donghui Wu; Xueping Zhang (Chinese Geographical Science, 2015)

Establishment and characterization of a gonad cell line from half-smooth tongue sole Cynoglossus semilaevis pseudomale - Ai Sun; Song-Lin Chen; Feng-Tao Gao; Hai-Long Li; Xiao-Feng Liu; Na Wang; Zhen-Xia Sha (Fish Physiology and Biochemistry, 2015)

Establishment and characterization of an ovarian cell line from half‐smooth tongue sole Cynoglossus semilaevis - A. Sun; T. Z. Wang; N. Wang; X. F. Liu; Z. X. Sha; S. L. Chen (Journal of Fish Biology, 2015)
A new ovarian cell line, CSO , was established from half‐smooth tongue sole Cynoglossus semilaevis . Primary culture of CSO cells was initiated from digestion of ovarian tissues pieces by trypsin solution and cultured at 24° C in Dulbecco's modified Eagle's medium– F12 medium ( DMEM – F12 , 1:1) (pH 7·0), supplemented with 20% foetal bovine serum, basic fibroblast growth factor ( bFGF ), epidermal growth factor ( EGF ), insulin‐like growth factor‐I ( IGF ‐I) and human chorionic gonadotropin ( HCG ). The cultured CSO cells, fibroblastic in morphology, proliferated to 100% confluency 3 days later and had been subcultured to passage 80. Chromosome analyses indicated that the CSO cells exhibited chromosomal aneuploidy with a modal chromosome number of 42 that displayed the normal diploid karyotype of C. semilaevis [2 n = 42 t, fundamental number ( N F ) = 42]. Reverse transcription polymerase chain reaction revealed that CSO cells could express ovarian somatic cell functional genes p 450 armo , foxl2 and sox9a but not ovary germ cell marker gene vasa and male‐specific gene dmrt1 . Transfection experiment demonstrated that CSO cells transfected with pEGFP‐N3 plasmid could express green fluorescence protein ( GFP ) with higher transfection efficiency. The CSO cell line might serve as a valuable tool for studies on the mechanism of sex determination and oogenesis of ovary in flatfish.

The altitudinal belts of subalpine virgin forest on Mt. Gongga simulated by a succession model - Gen-wei Cheng; Jian Sun; Yu-kun Sha; Ji-hui Fan (Journal of Mountain Science, 2014)

Genome-wide study of NAGNAG alternative splicing in Arabidopsis - Yanjing Shi; Guangli Sha; Xiaoyong Sun (Planta, 2014)

Oldest zircon xenocryst (4.17 Ga) from the North China Craton - Pei-Long Cui; Jing-Gui Sun; De-Ming Sha; Xi-Jing Wang; Peng Zhang; A-Lei Gu; Zhong-Yu Wang (International Geology Review, 2013)

Microbiota Regulates the TLR7 Signaling Pathway Against Respiratory Tract Influenza A Virus Infection - Sha Wu; Zhen-You Jiang; Yi-Fan Sun; Bin Yu; Jia Chen; Cong-Qi Dai; Xian-Lin Wu; Xiao-Long Tang; Xiao-Yin Chen (Current Microbiology, 2013)

Microparameter Prediction for a Triaxial Compression PFC3D Model of Rock Using Full Factorial Designs and Artificial Neural Networks - Miao-jun Sun; Hui-ming Tang; Xin-li Hu; Yun-feng Ge; Sha Lu (Geotechnical and Geological Engineering, 2013)

Groundwater Risk Assessment of the Third Aquifer in Tianjin City, China - Donglin Dong; Wenjie Sun; Zhaochang Zhu; Sha Xi; Gang Lin (Water Resources Management, 2013)

A conserved region in the 3′ untranslated region of the human LIMK1 gene is critical for proper expression of LIMK1 at the post-transcriptional level - Guang-Fei Deng; Shu-Jing Liu; Xun-Sha Sun; Wei-Wen Sun; Qi-Hua Zhao; Wei-Ping Liao; Yong-Hong Yi; Yue-Sheng Long (Neuroscience Bulletin, 2013)

Melanin in a Meristematic Mutant of Fonsecaea monophora Inhibits the Production of Nitric Oxide and Th1 Cytokines of Murine Macrophages - Junmin Zhang; Li Wang; Liyan Xi; Huaiqiu Huang; Yongxuan Hu; Xiqing Li; Xiao Huang; Sha Lu; Jiufeng Sun (Mycopathologia, 2013)

Genome-wide association study identified novel genetic variant on SLC45A3 gene associated with serum levels prostate-specific antigen (PSA) in a Chinese population - Jielin Sun; Sha Tao; Yong Gao; Tao Peng; Aihua Tan; Haiying Zhang; Xiaobo Yang; Xue Qin; Yanling Hu; Junjie Feng; Seong-Tae Kim; Xiaoling Lin; et al. (Human Genetics, 2013)

Effects of Formaldehyde Stress on Physiological Characteristics and Gene Expression Associated with Photosynthesis in Arabidopsis thaliana - Sha-Sha Wang; Zhong-Bang Song; Zhen Sun; Jing Zhang; Yan Mei; Hong-Juan Nian; Kun-Zhi Li; Li-Mei Chen (Plant Molecular Biology Reporter, 2012)

Optimization of Mine Drainage Capacity Using FEFLOW for the No. 14 Coal Seam of China’s Linnancang Coal Mine - Donglin Dong; Wenjie Sun; Sha Xi (Mine Water and the Environment, 2012)

Preparation of Rotigotine-Loaded Microspheres and Their Combination Use with L-DOPA to Modify Dyskinesias in 6-OHDA-Lesioned Rats - Aiping Wang; Lexi Wang; Kaoxiang Sun; Wanhui Liu; Chunjie Sha; Youxin Li (Pharmaceutical Research, 2012)

Overexpressions of dihydroxyacetone synthase and dihydroxyacetone kinase in chloroplasts install a novel photosynthetic HCHO-assimilation pathway in transgenic tobacco using modified Gateway entry vectors - Su-Qin Xiao; Zhen Sun; Sha-Sha Wang; Jing Zhang; Kun-Zhi Li; Li-Mei Chen (Acta Physiologiae Plantarum, 2012)

Genome-wide two-locus epistasis scans in prostate cancer using two European populations - Sha Tao; Junjie Feng; Timothy Webster; Guangfu Jin; Fang-Chi Hsu; Shyh-Huei Chen; Seong-Tae Kim; Zhong Wang; Zheng Zhang; Siqun L. Zheng; William B. Isaacs; Jianfeng Xu; et al. (Human Genetics, 2012)

Water-inrush Assessment Using a GIS-based Bayesian Network for the 12-2 Coal Seam of the Kailuan Donghuantuo Coal Mine in China - Dong Donglin; Sun Wenjie; Xi Sha (Mine Water and the Environment, 2012)

Erratum to: Physiological and transcriptional analysis of the effects of formaldehyde exposure on Arabidopsis thaliana - Sha-Sha Wang; Zhong-Bang Song; Zhen Sun; Jing Zhang; Yan Mei; Hong-Juan Nian; Kun-Zhi Li; Li-Mei Chen (Acta Physiologiae Plantarum, 2012)

Physiological and transcriptional analysis of the effects of formaldehyde exposure on Arabidopsis thaliana - Sha-Sha Wang; Zhong-Bang Song; Zhen Sun; Jing Zhang; Yan Mei; Hong-Juan Nian; Kun-Zhi Li; Li-Mei Chen (Acta Physiologiae Plantarum, 2012)

Immunohistochemical Study of Leucine-Enkephalin and Delta Opioid Receptor in Mantles and Feet of the Octopus Octopus ocellatus Gray - Ailong Sha; Hushan Sun; Yiyan Wang (International Journal of Peptide Research and Therapeutics, 2012)

A miRNA-492 binding-site polymorphism in BSG (basigin) confers risk to psoriasis in Central South Chinese population - Li-Sha Wu; Fang-Fang Li; Liang-Dan Sun; Dai Li; Juan Su; Ye-Hong Kuang; Gang Chen; Xiao-Ping Chen; Xiang Chen (Human Genetics, 2011)

The unsaturation of phosphatidylglycerol in thylakoid membrane alleviates PSII photoinhibition under chilling stress - Xiao-lin Sun; Sha Yang; Li-Yan Wang; Qiu-Yu Zhang; Shi-Jie Zhao; Qing-Wei Meng (Plant Cell Reports, 2011)

Identification of the transcriptional promoters in the proximal regions of human microRNA genes - Yue-Sheng Long; Guang-Fei Deng; Xun-Sha Sun; Yong-Hong Yi; Tao Su; Qi-Hua Zhao; Wei-Ping Liao (Molecular Biology Reports, 2011)

Promoter Analysis of Mouse Scn3a Gene and Regulation of the Promoter Activity by GC Box and CpG Methylation - Guang-Fei Deng; Jia-Ming Qin; Xun-Sha Sun; Zu-Ying Kuang; Tao Su; Qi-Hua Zhao; Yi-Wu Shi; Xiao-Rong Liu; Mei-Juan Yu; Yong-Hong Yi; Wei-Ping Liao; Yue-Sheng Long (Journal of Molecular Neuroscience, 2011)

Over-expression of StAPX in tobacco improves seed germination and increases early seedling tolerance to salinity and osmotic stresses - Wei-Hong Sun; Ming Duan; De-Feng Shu; Sha Yang; Qing-Wei Meng (Plant Cell Reports, 2010)

Human mesenchymal stem cells-like cells as cellular vehicles for delivery of immunotoxin in vitro - Chang-chen Hu; Yi-quan Ke; Xin-lin Sun; Xiao-dan Jiang; Ru-xiang Xu; Jun Lv; Yu-sheng Wang; Ying-qian Cai; Ling-sha Qin; Yu-xi Zou (Biotechnology Letters, 2009)

A new nor-lignan from the seeds of Descurainia sophia - Kai Sun; Xian Li; Wen Li; Jian-Ming Liu; Jin-Hui Wang; Yi Sha (Natural Product Research, 2006)